Electrophotographic member, process cartridge, and electrophotographic image forming apparatus
By designing an elastic layer with a matrix-domain structure and a surface layer containing an electronic conductive agent in the electrophotographic member, the excessive discharge and white spot image problems caused by accumulation of contaminants are solved, and high-quality image formation under high-speed processing and cleaner-free construction conditions are achieved.
Patent Information
- Application Number
- CN202411351592.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-09-27
- Filing Date
- 2024-09-26
- Publication Date
- 2025-03-28
AI Technical Summary
During the electrophotographic image formation process, contaminants such as toners and external additives accumulate on the charging member, resulting in excessive discharge and generation of white dot images, especially under harsh conditions of high-speed processing and cleaner-free configuration.
An electrophotographic member is used, which includes a base body having a conductive surface, an elastic layer on the conductive surface, and a surface layer. The elastic layer consists of an insulating first phase of the first rubber and a second phase containing a crosslinked product of the conductive particles and the second rubber, and has a matrix-domain structure. The surface layer contains an electronic conductive agent and has a specific impedance range under certain environmental conditions.
Even under dirt accumulation and harsh conditions, high-quality images can be formed for a long time, suppressing the generation of white dot images, and improving the performance of the electrophotographic image forming apparatus.
Smart Images

Figure CN119717431A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to an electrophotographic member, a process cartridge, and an electrophotographic image forming apparatus that can be used in an electrophotographic process. Background Art
[0002] The electrophotographic image forming apparatus includes a charging member, a transfer member, and a developing member. The charging member is a member that generates discharge between the charging member and the electrophotographic photosensitive member to charge the surface of the electrophotographic photosensitive member. The developing member is a member that controls the charge of the developer applied to the surface of the developing member by friction charging, provides a uniform charge amount distribution, and uniformly transfers the developer to the surface of the electrophotographic photosensitive member according to the applied electric field. The transfer member is a member that transfers the developer from the electrophotographic photosensitive member to a printing medium such as paper or an intermediate transfer member while generating discharge to stabilize the transferred developer.
[0003] In the electrophotographic image forming process, a latent image is drawn by charging the surface of a photosensitive member and then exposing the surface of the photosensitive member, a toner is transferred to the latent image on the surface of the photosensitive member by a developing member, and the toner is transferred to a paper medium by a transfer member. When transferring to a paper medium, the toner remaining on the photosensitive member without being transferred to the paper (hereinafter also referred to as "transfer residual toner") is scraped off by a cleaning member to be removed from the surface of the photosensitive member.
[0004] However, when the cleaning member cannot completely scrape off the toner, the toner or external additives adhere to the surface of the charging member as contaminants, and overdischarge occurs due to the contaminants, thereby generating a whitespot-like image (hereinafter also referred to as a "whitespot image").
[0005] Japanese Patent Application Laid-Open No. 2021-067946 discloses a charging member in which electric charge is uniformly applied to pollutants attached to the surface of the charging member, and the pollutants are discharged from the surface of the charging member to the surface of the photosensitive member to suppress the accumulation of pollutants on the surface of the charging member. The charging member has a surface layer formed on an elastic layer, and the elastic layer has a matrix-domain structure in which domains containing a second rubber and a conductive agent are dispersed in a matrix containing a first rubber. Summary of the invention
[0006] In recent years, the electrophotographic image forming method has been further improved in speed and service life, and an electrophotographic image forming apparatus having a configuration (hereinafter also referred to as a "cleaner-free configuration") that does not include a cleaning member for removing transfer residual toner remaining on a photosensitive member to miniaturize the apparatus has also been provided. When the present inventors performed durability evaluation in high-speed processing and a cleaner-free configuration using the charging member of Japanese Patent Application Laid-Open No. 2021-067946, the accumulation of pollutants on the charging member became significant at a number of prints where the accumulation of pollutants was not a problem previously, and sometimes a white spot image was generated due to excessive discharge caused by the pollutants.
[0007] At least one aspect of the present disclosure relates to an electrophotographic member capable of forming high-quality images for a long time even under harsh conditions of accumulation of dirt on the electrophotographic member, i.e., further accelerating the electrophotographic image forming process and a cleaner-free configuration. In addition, at least one aspect of the present disclosure relates to a process cartridge that facilitates high-quality electrophotographic image formation. In addition, at least one aspect of the present disclosure relates to an electrophotographic image forming apparatus capable of forming high-quality electrophotographic images.
[0008] According to at least one aspect of the present disclosure, there is provided an electrophotographic member, comprising:
[0009] A substrate having a conductive surface;
[0010] an elastic layer on the conductive surface of the substrate; and
[0011] a surface layer in contact with a surface of the elastic layer on the side opposite to the surface facing the substrate, wherein
[0012] The surface layer contains an electronically conductive agent,
[0013] The metal film is provided on the outer surface of the surface layer of the electrophotographic member, and in an environment of a temperature of 23°C and a relative humidity of 50%, when an alternating voltage with an amplitude of 1 V and a frequency of 1.0 Hz is applied, the impedance between the conductive surface of the substrate and the metal film is within 1.0×10 3 to 1.0×10 8 In the range of Ω,
[0014] The elastic layer includes an insulating first phase including at least a cross-linked product of a first rubber, and a second phase including conductive particles and a cross-linked product of a second rubber different from the first rubber,
[0015] The thickness of the elastic layer is at least 10 μm,
[0016] The elastic layer has a matrix-domain structure in which domains composed of the second phase are dispersed in a matrix composed of the first phase in a region of at least 5 μm in the depth direction of the elastic layer from the interface between the elastic layer and the surface layer,
[0017] When a region having a thickness of 1 μm from the interface between the elastic layer and the surface layer to a position of 1 μm in the depth direction of the elastic layer is defined as region A, and a region having a thickness of 1 μm from the interface to a position of 5 to 6 μm in the depth direction of the elastic layer is defined as region B, and
[0018] The first surface of the elastic layer in region A is exposed, and a first observation region of a square with a side length of 100 μm is placed on the first surface by a scanning electron microscope, wherein the first observation region includes at least the second phase.
[0019] The ratio (AR12 / AR11) of the total area AR12 of the second phase in the first observation region to the area AR11 of the first observation region is greater than 0.40, and
[0020] When the second surface of the elastic layer in the region B was exposed and a second observation region of a square with a side length of 100 μm was placed on the second surface by a scanning electron microscope, a matrix-domain structure was observed in the second observation region, and the ratio (AR22 / AR21) of the total area AR22 of the second phase in the second observation region to the area AR21 of the second observation region was 0.40 or less.
[0021] According to at least one aspect of the present disclosure, there is provided a process cartridge detachable from an electrophotographic image forming apparatus, the process cartridge including the above-described electrophotographic member.
[0022] According to at least one aspect of the present disclosure, there is provided an electrophotographic image forming apparatus including the above-mentioned electrophotographic member.
[0023] According to at least one aspect of the present disclosure, an electrophotographic component can be provided, which can form high-quality images for a long time even under harsh conditions of accumulation of dirt on the electrophotographic component, that is, further accelerating the electrophotographic image forming process and the cleaner-free structure. According to at least one aspect of the present disclosure, a processing box that facilitates high-quality electrophotographic image formation can be provided. In addition, according to at least one aspect of the present disclosure, an electrophotographic image forming device capable of forming high-quality electrophotographic images can be provided.
[0024] Further features of the present invention will become apparent from the following description of exemplary embodiments with reference to the attached drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 is a cross-sectional view of the conductive roller;
[0026] Figure 2 is a schematic diagram of a crosshead extruder;
[0027] Figure 3 is a schematic cross-sectional view of a process cartridge; and
[0028] Figure 4 is a schematic diagram of an electrophotographic image forming apparatus. DETAILED DESCRIPTION
[0029] In the present disclosure, unless otherwise specified, the expression "from XX to YY" or "XX to YY (XX to YY)" indicating a numerical range refers to a numerical range including a lower limit and an upper limit as endpoints. In addition, when a numerical range is described in a segmented manner, the upper limit and the lower limit of each numerical range can be arbitrarily combined. In addition, in the present disclosure, for example, descriptions such as "at least one selected from the group consisting of XX, YY and ZZ" refer to any one of XX, YY, ZZ, a combination of XX and YY, a combination of XX and ZZ, a combination of YY and ZZ, and a combination of XX, YY and ZZ.
[0030] The present inventors studied the cause of the appearance of white spots on electronic photographic images in the charging member according to Japanese Patent Application Laid-Open No. 2021-067946, and found that with increased processing speed and in a cleaner-free structure, the accumulation of pollutants such as colorants and external additives on the charging member becomes significant at the number of prints where the accumulation of pollutants was not a problem previously.
[0031] First, the process of attaching pollutants such as toners and external additives to the surface of the charging member will be described. Since the toners and external additives must have a certain charge so that the toners and external additives can be properly transferred to the photosensitive member during the development process, the toners and external additives generally have insulating properties. Therefore, the toners and external additives as pollutants also have insulating properties. In the developer container, the toners and external additives are charged to a large extent with a positive or negative polarity. On the other hand, the pollutants of the toners or external additives that are not transferred to the paper or the intermediate transfer member and remain on the photosensitive drum are affected by friction, etc. before reaching the charging member, and are therefore charged with a constant distribution relative to the positive and negative polarities.
[0032] On the other hand, the charging member is configured to discharge relative to the photosensitive member. Specifically, a DC voltage is applied to the charging member to generate a potential difference between the charging member and the surface of the photosensitive member. In this case, with respect to the potential difference between the charging member and the photosensitive member, it is difficult to avoid that a contaminant component having a polarity opposite to that of the charging bias voltage adheres to the charging member side due to electrostatic attraction, and the contaminant is transferred from the photosensitive member to the charging member.
[0033] Next, a white spot image generated due to abnormal discharge caused by contaminants is described. Discharge occurs between the charging member and the photosensitive member in accordance with Paschen's law, and the surface of the photosensitive member is negatively or positively charged according to the applied voltage. Since the discharge occurs by ionization of neutral air in the electric field, charges of opposite polarity are also generated at the same time. That is, while the photosensitive member is negatively or positively charged by the discharge, charges of opposite polarity to the charges used to charge the photosensitive member are also introduced to the charging member by the electric field.
[0034] In the case where the charging member is contaminated with insulating contaminants, the charges of the opposite polarity toward the charging member do not escape from the surface of the charging member toward the substrate side, but are captured on the surface, and therefore, the contaminants attached to the surface of the charging member are charged with the opposite polarity. The charges of the opposite polarity exist at a very short distance between the contaminants charged with the opposite polarity and the surrounding area of the area where the contaminants are attached. Therefore, an extremely strong electric field is generated, and due to the extremely strong electric field, abnormal overdischarge occurs, and a white spot image is generated.
[0035] Next, the "discharge" phenomenon in which pollutants attached to the surface of the charging member are returned to the photosensitive member is explained. When pollutants are attached to the charging member, due to the negative or positive bias applied to the charging member, electric charges having the same polarity as the applied bias are gradually applied to the pollutants from the outer surface. When the electric charges are sufficiently accumulated in the pollutants, the electrostatic force acts through the electric field formed from the surface of the charging member toward the photosensitive drum, and exceeds the adhesion force between the surface of the charging member and the pollutants, and accordingly, the "discharge" phenomenon occurs in which the pollutants are separated from the surface of the charging member and transferred to the photosensitive member side. That is, when the electric charges are sufficiently accumulated in most of the pollutants and the discharge phenomenon occurs effectively, the accumulation of pollutants can be prevented.
[0036] As described above, the charging member of Japanese Patent Application Laid-Open No. 2021-067946 has a structure in which an electronic conductive agent is added to a surface layer in an elastic layer having a matrix-domain structure. On the outer peripheral surface of the domain in the matrix-domain structure, since there are almost no bumps and the domain is almost spherical, it is difficult to generate a concentrated point of electron exchange between domains. In addition, due to the presence of a conductive surface layer in which an electronic conductive agent is dispersed, a charge having the same polarity as the applied bias can be uniformly applied to the pollutant.
[0037] However, in the charging member of Japanese Patent Application Laid-Open No. 2021-067946, there is a case where a region is formed in which the domain in the elastic layer is less connected to the conductive path in the surface layer by means of conductive particles. In this case, the charge stagnates at the interface between the elastic layer and the surface layer, and sufficient charge cannot be applied to the pollutants, and the pollutants are not discharged but accumulated. This phenomenon is significant during acceleration. In addition, in the case of a cleaner-free structure, there are a lot of pollutants that migrate to the surface of the charging member as transfer residual toners, etc. Therefore, it is impossible to apply a charge of the same polarity as the applied bias to all the pollutants, and some pollutants that cannot be discharged to the photosensitive member remain, and accumulation of pollutants occurs.
[0038] Based on the above, the inventors have recognized that it is necessary to more effectively perform charge exchange between the domains in the elastic layer and the conductive paths in the surface layer by means of conductive particles in the above structure in order to suppress the accumulation of pollutants in the accelerated process and the cleaner-less structure. Based on such recognition, the inventors have further studied and found that in an electrophotographic member including a substrate having a conductive surface, an elastic layer on the conductive surface of the substrate, and a surface layer in contact with a surface on the side opposite to the surface facing the substrate of the elastic layer, by satisfying all of the following requirements (A) to (D), the generation of white spot images can be suppressed for a long time even under severe conditions of contamination such as high-speed processes and cleaner-less structures.
[0039] Requirement (A)
[0040] When a metal film is provided on the outer surface of the surface layer of the electrophotographic member and an AC voltage with an amplitude of 1 V and a frequency of 1.0 Hz is applied between the conductive surface of the substrate and the metal film in an environment with a temperature of 23°C and a relative humidity of 50%, the impedance is 1.0×10 3 to 1.0×10 8 Ω.
[0041] Requirement (B)
[0042] The elastic layer includes an insulating first phase containing at least a first rubber and a second phase containing a second rubber different from the first rubber and conductive particles, and the thickness of the elastic layer is 10 μm or more. A region having a thickness of 1 μm from an interface between the elastic layer and the surface layer to a position of 1 μm in the depth direction of the elastic layer is defined as region A. When the first surface in region A is exposed and a first observation region of a square having a side length of 100 μm is placed on the first surface by a scanning electron microscope, the first observation region includes at least a second phase containing the second rubber and conductive particles. A ratio (AR12 / AR11) of a total area AR12 of an area of the second phase in the first observation region to an area AR11 of the first observation region is greater than 0.40.
[0043] Requirement (C)
[0044] The elastic layer has a matrix-domain structure in which domains composed of a second phase are dispersed in a matrix composed of a first phase in a region of 5 μm or more along the depth direction of the elastic layer from the interface between the elastic layer and the surface layer. A region with a thickness of 1 μm from the interface between the elastic layer and the surface layer to a position of 5 μm to 6 μm along the depth direction of the elastic layer is defined as region B. When the second surface in region B is exposed and a second observation region of a square with a side length of 100 μm is placed on the second surface by a scanning electron microscope, a matrix-domain structure is observed in the second observation region. In addition, the ratio (AR22 / AR21) of the total area AR22 of the area of the second phase in the second observation region to the area AR21 of the second observation region is 0.40 or less.
[0045] Requirement (D)
[0046] The surface layer contains an electronically conductive agent.
[0047] Each requirement is described in detail below.
[0048] Requirement (A)
[0049] Requirement (A) indicates the degree of conductivity of the electrophotographic member. An electrophotographic member showing such an impedance value can suppress an excessive increase in the discharge current, and as a result, can prevent the occurrence of potential unevenness in charging due to abnormal discharge. In addition, it can suppress the shortage of injected charge supplied to the contaminant. The impedance is preferably 1.0×10 4 to 1.0×10 7 Ω.
[0050] The impedance can be controlled by the volume resistivity of the domains and the amount of domains in the matrix-domain structure.
[0051] The impedance according to requirement (A) can be measured by the following method.
[0052] First, in order to eliminate the influence of contact resistance between the electrophotographic member and the measuring electrode, a low resistance film was deposited on the outer surface of the surface layer of the electrophotographic member, used as an electrode, and impedance was measured with two terminals using a conductive substrate as a ground electrode.
[0053] Examples of the method of forming a thin film include methods of forming a metal film such as metal evaporation, sputtering, coating of a metal paste, and attachment of a metal tape. Among them, a method of forming a metal film such as platinum or palladium as an electrode by evaporation is preferred from the viewpoint of reducing the contact resistance with the electrophotographic member. In the present disclosure, a platinum metal film is used.
[0054] When a metal film is formed on the surface of an electrophotographic member, it is preferred to provide a mechanism capable of holding the electrophotographic member in the vacuum evaporation apparatus in consideration of the convenience and uniformity of the thin film. In addition, it is preferred to use a vacuum evaporation apparatus further provided with a rotating mechanism for an electrophotographic member having a cylindrical cross section.
[0055] For example, for a cylindrical electrophotographic member having a cross section formed by a curved surface such as a circle, it is difficult to connect a metal film as a measuring electrode and an impedance measuring device, so the following method is preferably used. Specifically, after an electrode of a metal film having a width of 10 to 20 mm is formed in the length direction of the electrophotographic member, a metal sheet can be wound without a gap, and the metal sheet can be connected to a measuring electrode output from a measuring device for measurement. Thus, an electrical signal from the surface layer of the electrophotographic member can be appropriately acquired by the measuring device, and impedance measurement can be performed. When measuring impedance, the metal sheet can be a metal sheet having the same resistance value as the metal portion of the connecting cable of the measuring device, for example, aluminum foil or a metal tape can be used.
[0056] The impedance measurement device can be capable of measuring up to 1.0×10 7 Any device that measures impedance in the frequency domain of Hz, such as an impedance analyzer, a network analyzer, or a spectrum analyzer. Among them, it is preferred to measure from the resistance area of the electrophotographic member by an impedance analyzer.
[0057] The impedance measurement conditions are described. The impedance in the frequency domain of 1.0 Hz is measured using an impedance measuring device (e.g., trade name "Solartron1260", 96W dielectric impedance measurement system, manufactured by Solartron Metrology). The measurement is performed in an environment where the temperature is 23°C and the relative humidity is 50%. The amplitude of the AC voltage is 1 Vpp. The 5 regions are divided into 5 equal parts in the length direction of the electronic photographic member, and 1 measurement is performed in each region, i.e. 5 times in total. The average value is taken as the impedance of the electronic photographic member. More specific steps of the measurement will be described later.
[0058] Requirement (B)
[0059] Requirement (B) is a requirement indicating the state of the vicinity of the outer surface of the elastic layer. The vicinity of the outer surface is a region with a thickness of 1 μm from the interface between the elastic layer and the surface layer to a position of 1 μm in the depth direction of the elastic layer, and this region is referred to as region A. As described in requirement (C) below, region B excluding the outer surface in the elastic layer refers to a region with a thickness of 1 μm from the interface between the elastic layer and the surface layer to a position of 5 to 6 μm in the depth direction of the elastic layer.
[0060] In a region of 5 μm or more in the depth direction of the elastic layer from the interface between the elastic layer and the surface layer including the region B, the elastic layer has a matrix-domain structure in which domains composed of a second phase containing conductive particles and a cross-linked product of a second rubber different from the first rubber are dispersed in a matrix composed of an insulating first phase containing a cross-linked product of the first rubber. The ratio (AR22 / AR21) is 0.40 or less. On the other hand, in the region A near the outer surface of the elastic layer, the ratio (AR12 / AR11) is greater than 0.40. The region A may not have the matrix-domain structure in which the domains of the second phase are dispersed in the matrix of the first phase, and may have an inverted structure in which the first phase is dispersed in the second phase.
[0061] In the matrix-domain structure, charges can be accumulated on the interface side with the matrix in the domain, and after the charges on the surface of the electrophotographic member are consumed by discharge, the charges accumulated in the domain are rapidly transferred to the surface of the electrophotographic member. However, when the entire elastic layer has the matrix-domain structure, at the interface between the surface layer and the elastic layer, the charge exchange between the matrix portion in the elastic layer and the conductive path in the surface layer by the electron conductive agent does not function well, and the charges stagnate. After the charges on the surface of the electrophotographic member are consumed by discharge, it becomes difficult to rapidly transfer the charges to the surface of the electrophotographic member.
[0062] Therefore, after the discharge at the upstream of the nip portion relative to the contact portion between the electrophotographic member and the photosensitive member (hereinafter, also referred to as the "nip portion"), the effect of applying the charge of the same polarity as the applied voltage to the pollutants in the nip portion cannot be fully obtained. As a result, the ability to discharge the pollutants to the photosensitive member is reduced, and the pollutants are accumulated on the surface of the electrophotographic member. This phenomenon is easy to become significant in an accelerated process in which the time from the discharge upstream to the passing through the nip is short, or in the case where there are many pollutants to be charged.
[0063] In order to suppress the stagnation of charge transfer at the elastic layer / surface layer interface, a configuration in which the amount of the second phase as the domain at the elastic layer / surface layer interface is large is preferred. However, although the details will be described in requirement (C) later, the increase in the amount of domains in the entire region within the elastic layer causes the domains to be connected over a wide range, and charges cannot be accumulated within the domains, so the charge application performance to the pollutants is deteriorated.
[0064] Therefore, it is important that the amount of the second phase is large only in region A near the outer surface of the elastic layer forming an interface with the surface layer, and that the amount of the second phase in region B as another elastic layer region is an amount that allows the second phases to form domains without being connected to each other.
[0065] Under the above configuration, the charge exchange from the second phase in the elastic layer to the conductive path via the electron conductive agent can be efficiently performed in the surface layer. As a result, after the charge on the surface of the electrophotographic member is consumed by the discharge in the upstream portion of the nip portion, the charge can be quickly transferred to the surface of the electrophotographic member in the time until the electrophotographic member reaches the nip portion, and even in the above-mentioned short time acceleration subject, sufficient charge can be applied to the contaminant in the nip portion.
[0066] For the ratio of the second phase in the elastic layer at the outer surface of the elastic layer, a plane parallel to the length direction is cut out from the surface layer side of the electrophotographic member, and the surface of the elastic layer in region A is observed with a scanning electron microscope to calculate the area of the second phase. Specifically, when the total area of the first phase and the second phase, that is, the area of the entire first observation region is defined as AR11, and the area of the domain is defined as AR12, AR12 / AR11 needs to be greater than 0.40. AR12 / AR11 is preferably 0.50 to 0.75, and more preferably 0.60 to 0.75.
[0067] The thickness of the elastic layer is 10 μm or more. The thickness of the elastic layer may be 10 μm or more, and the upper limit is not particularly limited. The thickness of the elastic layer is preferably 1.0 to 2.0 mm.
[0068] Requirement (C)
[0069] Requirement (C) is a requirement indicating the state of the elastic layer in the region excluding the vicinity of the outer surface of the elastic layer in the elastic layer. Specifically, this refers to a region having a depth of 5 μm or more in the depth direction of the elastic layer from the elastic layer / surface layer interface. Furthermore, in a region (region B) having a thickness of 1 μm between a position of 5 μm in the depth direction of the elastic layer from the elastic layer / surface layer interface and a position of 6 μm in the depth direction of the elastic layer, the presence of the second phase is typically observed.
[0070] A region of 5 μm or more in the depth direction of the elastic layer from the interface between the elastic layer and the surface layer including the region B has a matrix-domain structure in which domains are dispersed in the matrix. In the region B, the ratio of the second phase (domain ratio) is 40% or less, that is, AR22 / AR21 is 0.40 or less.
[0071] When AR22 / AR21 is 0.40 or more, most domains can be connected to each other. Since the domains are connected to each other, the charge transfer phenomenon between the domains becomes dominant over the phenomenon of charge accumulation on the matrix interface side in the domain, and overdischarge may occur upstream of the roller gap. Since the charge cannot be accumulated on the matrix interface side in the domain, the charge on the surface of the electrophotographic member cannot be quickly resupplied to the surface of the electrophotographic member after being largely consumed due to overdischarge, so sufficient charge application to the pollutant cannot be performed in the roller gap. As a result, the pollutant cannot be fully discharged to the photosensitive member, and the accumulation of the pollutant becomes obvious. In addition, white spots are easily generated.
[0072] For the ratio of the domain in region B, a plane parallel to the length direction is cut out from the surface layer side of the electrophotographic member, and in region B, the arbitrarily cut surface is observed with a scanning electron microscope to calculate the area of the matrix part and the domain part. Specifically, when the total area of the matrix part and the domain part, that is, the area of the entire second observation area is defined as AR21, and the area of the second phase capable of forming a domain is defined as AR22, AR22 / AR21 is 0.40 or less. AR22 / AR21 is preferably 0.15 to 0.40, and more preferably 0.20 to 0.40.
[0073] In addition, it is preferred that in region B, there are few convex and concave portions on the peripheral surface of the domains dispersed in the matrix. When there are few concave and convex portions on the peripheral surface of the domains, there is almost no low density in the charge exchange between the domains, and the charge supply to the surface of the electrophotographic member becomes more uniform. This is because when the charge exchange is concentrated on the convex portions and a portion where the charge exchange is concentrated is formed in a part, a portion where the charge exchange is insufficient is also generated at the same time. As a result, the charge can be uniformly applied to the pollutants, and the accumulation of the pollutants can be more easily suppressed. In addition, it is easier to suppress white spots.
[0074] Specifically, it can be determined as follows that the number of convex portions and concave portions on the outer peripheral surface of the domain is small. The second surface in region B is exposed, and a 15 μm square observation area is placed on the second surface in region B by a scanning electron microscope, and the perimeter of the domain is defined as A, and the envelope perimeter of the domain is defined as B. At this time, the number ratio of domains with an A / B value of 1.00 to 1.10 is preferably 80% by number or more, and more preferably 88 to 98% by number.
[0075] The arithmetic mean value of A / B is preferably 1.00 to 1.10, more preferably 1.00 to 1.07.
[0076] In addition, when the second surface in area B is exposed and a 15 μm square observation area is placed on the second surface in area B by a scanning electron microscope and the domain is observed, the number average value of the circle equivalent diameter of the domain is preferably 0.2 to 3.0 μm, and more preferably 0.4 to 2.0 μm.
[0077] Request (D)
[0078] Requirement (D) is a requirement for the surface layer. In the absence of a surface layer, the contact area between the toner and the elastic layer is small, and when the contact portion is the base portion of the elastic layer, the charge applied to the contaminant may be insufficient.
[0079] In addition, when the surface layer is ionically conductive, because the environmental dependence increases, sufficient conductivity cannot be obtained in a low-temperature and low-humidity environment where overdischarge due to pollutants may usually occur, and the charge responsiveness is slow, so that sufficient charge cannot be applied to the pollutants in a short time during the acceleration process. Therefore, the surface layer is required to contain an electronic conductive agent.
[0080] A conductive roller will be used as an example reference Figure 1 An electrophotographic member is described. Figure 1 The conductive roller includes a substrate 11 having a cylindrical conductive surface, an elastic layer 12 formed on the outer peripheral surface of the substrate 11, and a surface layer 13 in contact with the surface of the elastic layer 12 opposite to the surface facing the substrate 11.
[0081] Substrate (support) having a conductive surface
[0082] The material constituting the substrate 11 can be appropriately selected from materials known in the field of electrophotographic conductive members and materials that can be used as conductive members. Examples thereof include metals or alloys such as aluminum, stainless steel, conductive synthetic resins, iron and copper alloys.
[0083] In addition, the substrate may be oxidized or plated with chromium or nickel. As the type of plating, electroplating or chemical plating may be used. From the viewpoint of dimensional stability, chemical plating is preferred. Examples of chemical plating used herein include nickel plating, copper plating, gold plating, and various other alloy platings.
[0084] The plating thickness is preferably 0.05 μm or more, and considering the balance between working efficiency and rust prevention ability, the plating thickness is preferably 0.10 to 30.00 μm. The cylindrical shape of the substrate 11 can be a solid cylindrical shape or a hollow cylindrical shape (cylindrical shape). The outer diameter of the substrate is preferably in the range of 3 to 10 mm.
[0085] Furthermore, processing of a portion for mounting to an electrophotographic apparatus is performed as necessary. When a medium resistance layer or an insulating layer exists between the substrate and the elastic layer, charges cannot be quickly supplied after charges are consumed by discharge. Therefore, it is preferable that the elastic layer is provided directly on the substrate or provided only on the periphery of the substrate via an intermediate layer including a film such as a primer and a conductive resin layer.
[0086] As the primer, a known primer can be selected and used according to the rubber material for forming the elastic layer, the material of the substrate, etc. Examples of the material of the primer include thermosetting resins and thermoplastic resins, and specifically, known materials such as phenolic resins, polyurethane resins, acrylic resins, polyester resins, polyether resins, and epoxy resins can be used.
[0087] Elastic layer
[0088] The elastic layer includes an insulating first phase including at least a cross-linked product of a first rubber, and a second phase including a cross-linked product of a second rubber different from the first rubber and conductive particles. The elastic layer has a matrix-domain structure in which domains composed of the second phase are dispersed in a matrix composed of the first phase in a region of 5 μm or more in a depth direction of the elastic layer from an interface between the elastic layer and a surface layer. Although the details will be described below, in order to satisfy requirement (B), it is preferred that the SP value ((J / cm 3 ) 0.5 ), and the difference in SP value is preferably 3.0 or less, and more preferably 1.0 or less.
[0089] Matrix
[0090] The matrix includes the first rubber. The volume resistivity ρm of the matrix in region B is preferably 1.0×10 8 ~1.0×10 17 Ωcm. By setting the volume resistivity of the matrix to 1.0×10 8 Ωcm or more, the matrix can suppress the destruction of charge exchange between conductive domains. In addition, by setting the volume resistivity ρm to 1.0×10 17 When the thickness is Ωcm or less, when a charging bias is applied between the substrate and the charged member, discharge from the electrophotographic member to the charged member can be smoothly performed.
[0091] The volume resistivity ρm of the matrix is preferably 1.0×10 8 ~1.0×10 15 Ωcm, more preferably 1.0×10 8 ~1.0×10 14 Ωcm. A method for measuring the volume resistivity ρm of the matrix will be described below.
[0092] The volume resistivity ρm of the matrix can be controlled by the volume resistivity of the first rubber used for the matrix.
[0093] First Rubber
[0094] The first rubber is the component with the largest blending ratio in the rubber composition for forming the elastic layer, and the cross-linked product of the first rubber determines the mechanical strength of the elastic layer. Therefore, as the first rubber, for the elastic layer after cross-linking, a rubber that exhibits the strength required for the conductive member for electrophotography is used. Preferred examples of the first rubber are as follows. Natural rubber (NR), isoprene rubber (IR), butadiene rubber (BR), styrene-butadiene rubber (SBR), butyl rubber (IIR), ethylene-propylene rubber (EPM), ethylene-propylene-diene terpolymer rubber (EPDM), chloroprene rubber (CR), acrylonitrile-butadiene rubber (NBR), hydrogenated NBR (H-NBR) and silicone rubber.
[0095] The first rubber preferably includes at least one selected from the group consisting of isoprene rubber (IR), butadiene rubber (BR), styrene-butadiene rubber (SBR) and acrylonitrile-butadiene rubber (NBR), and more preferably includes at least one selected from the group consisting of styrene-butadiene rubber (SBR) and acrylonitrile-butadiene rubber (NBR).
[0096] The first rubber forming the matrix may contain reinforcing materials to the extent that the conductivity is not affected. Examples of reinforcing materials include reinforcing carbon black having low conductivity. Specific examples of reinforcing carbon black include FEF, GPF, SRF, and MT carbon, etc.
[0097] Furthermore, fillers such as calcium carbonate, processing aids, vulcanization aids, vulcanization accelerators, vulcanization accelerating aids, vulcanization retarders, anti-aging agents, softeners, dispersants, colorants, etc. may be added to the first rubber as needed.
[0098] domain
[0099] The domain comprises a cross-linked product of a second rubber different from the first rubber and conductive particles. Here, conductivity is defined as a volume resistivity of less than 1.0×10 8 Ωcm. On the other hand, insulation refers to the volume resistivity of 1.0×10 8 Ωcm or more.
[0100] Second Rubber
[0101] As specific examples of the second rubber, for example, it is preferably at least one selected from the group consisting of natural rubber (NR), isoprene rubber (IR), butadiene rubber (BR), acrylonitrile butadiene rubber (NBR), styrene butadiene rubber (SBR), butyl rubber (IIR), ethylene propylene rubber (EPM), ethylene-propylene-diene rubber (EPDM), chloroprene rubber (CR), nitrile rubber (NBR), hydrogenated nitrile rubber (H-NBR), silicone rubber and polyurethane rubber (U).
[0102] The second rubber preferably includes at least one selected from the group consisting of isoprene rubber (IR), butadiene rubber (BR), styrene-butadiene rubber (SBR), acrylonitrile-butadiene rubber (NBR) and ethylene-propylene-diene rubber (EPDM), and more preferably includes at least one selected from the group consisting of styrene-butadiene rubber (SBR), acrylonitrile-butadiene rubber (NBR) and ethylene-propylene-diene rubber (EPDM).
[0103] Conductive particles
[0104] Examples of the conductive particles include, for example, carbon materials such as conductive carbon black or graphite, conductive oxides such as titanium oxide or tin oxide, metals such as Cu or Ag, particles of electronic conductive agents such as conductive oxides, or particles of electronic conductive agents such as particles coated with conductive oxides or metals on the surface to become conductive. Two or more of these conductive particles may be appropriately blended and used.
[0105] The cross-sectional area S of the conductive particles in region B C The ratio S to the cross-sectional area S of the domain C / S is preferably 20.0 to 30.0%, more preferably 25.0 to 30.0%. By filling the domain with conductive particles at a high density in this way, it is easy to make the outer surface of the domain less uneven. The upper limit of the ratio of the cross-sectional area of the conductive particles to the cross-sectional area of the domain is not particularly limited, but is preferably 30.0% or less.
[0106] In order to obtain a domain densely filled with conductive particles, conductive carbon black is preferably used as the conductive particles. That is, the conductive particles preferably include carbon black. The carbon black is preferably at least one selected from the group consisting of, for example, gas furnace black, oil furnace black, thermal black, lamp black, acetylene black and Ketjen black.
[0107] Among them, DBP absorption of 40 to 80 cm 3 / 100g of carbon black. DBP absorption (cm 3 / 100g) is the volume of dibutyl phthalate (DBP) that can absorb 100g of carbon black, and is measured according to Japanese Industrial Standard (JIS) K6217-4:2017 (Carbon black for rubber - Basic properties - Part 4: Determination of oil absorption (including compressed samples)). Generally, carbon black has a clustered high-order structure in which primary particles with an average particle size of 10 to 50nm are aggregated. This clustered high-order structure is called a structure, and its degree is measured by the DBP absorption (cm 3 / 100g) to quantify.
[0108] Generally, carbon black with a developed structure has high reinforcing properties for rubber, is difficult to introduce into rubber, and has very high shear torque during kneading. Therefore, it is difficult to increase the filling amount in the domain.
[0109] On the other hand, the conductive carbon black having a DBP absorption within the above range has an underdeveloped structure, so the carbon black aggregates less and has good dispersibility in the rubber. Therefore, the filling amount in the domain can be increased, and as a result, a domain with an outer shape closer to a sphere is easily obtained.
[0110] In addition, in carbon black that develops the structure, carbon black easily aggregates with each other, and the aggregates easily become large blocks with a concavo-convex structure. On the other hand, conductive carbon black having a DBP absorption within the above range is preferred because it is difficult to form aggregates. The content of conductive particles such as conductive carbon black is preferably 20 to 150 parts by mass relative to 100 parts by mass of the second rubber contained in the domain. The content is more preferably 50 to 100 parts by mass.
[0111] The volume resistivity of the domain is preferably 1.0×10 4 Ωcm or less. When the volume fraction is 1.0×10 4 When the volume fraction of the domain that stably forms the matrix-domain structure is less than Ωcm, the conductivity can be carried out. The volume resistivity of the domain can be measured by the same method as all the methods for measuring the volume resistivity of the matrix, except that the measurement position is changed to the position corresponding to the domain and the applied voltage when measuring the current value is changed to 1V.
[0112] In order to obtain the electrophotographic member defined in requirement (A), the average value of the number of domains in the 15 μm square observation area placed in region B is preferably 20 to 300, and more preferably 40 to 300. When the length in the longitudinal direction of the elastic layer is L, the observation area is a 15 μm square area placed in region B by cutting out planes parallel to the longitudinal direction of the electrophotographic member from the surface layer side at three positions of L1 / 4, L2 / 4 and L3 / 4. The arithmetic average value of these three observation areas is adopted.
[0113] When the number of domains is 20 or more, sufficient conductivity can be obtained as an electrophotographic member, and sufficient charge supply can be achieved even in a high-speed process. In addition, when the number is 300 or less, a sufficient distance between domains can be maintained, and aggregation of domains caused by repetition of image output can be suppressed, so that uniform discharge can be easily achieved.
[0114] Method for manufacturing elastic layer
[0115] The elastic layer of the electrophotographic member can be formed, for example, by a method comprising the following steps (i) to (iv).
[0116] Step (i): a step of preparing a domain-forming rubber composition (hereinafter, also referred to as “CMB”) containing conductive particles and a second rubber.
[0117] Step (ii): a step of preparing a matrix-forming rubber composition (hereinafter also referred to as “MRC”) containing a first rubber.
[0118] Step (iii): a step of kneading CMB and MRC to prepare a rubber composition for forming an elastic layer having a matrix-domain structure.
[0119] Step (iv): a step of forming a layer of the elastic layer-forming rubber composition prepared in step (iii) on a substrate directly or via another layer, and curing the rubber composition layer to form an elastic layer.
[0120] The mixing ratio of CMB to MRC by mass (CMB:MRC) in the rubber composition for elastic layer formation is preferably 10:90 to 40:60, more preferably 20:80 to 30:70. The rubber composition for elastic layer formation may contain known additives such as a vulcanizing agent and a vulcanization accelerator as required. The elastic layer is, for example, a crosslinked product (vulcanized product) of the rubber composition for elastic layer formation.
[0121] In order to obtain a domain satisfying requirement (C), it is effective to add a large amount of DBP having a DBP absorption of preferably 40 to 170 cm 3 / 100g, more preferably 40 to 90cm 3 / 100g of carbon black is added, and the mixture is kneaded as conductive particles for preparing CMB to prepare CMB. In this case, the blending amount of carbon black in CMB is preferably 40 to 200 parts by mass relative to the second rubber, for example, relative to 100 parts by mass of the second rubber. In particular, the content is preferably 50 to 100 parts by mass.
[0122] The ratio of the cross-section of the conductive particles in the domain to the cross-sectional area of the domain can be measured as follows. First, a thin sheet of the elastic layer is prepared. In order to properly observe the matrix-domain structure, a pretreatment such as a dyeing treatment or a deposition treatment may be performed to properly obtain the contrast between the conductive phase and the insulating phase.
[0123] The thin slices subjected to cross-section formation and pretreatment can be observed using a scanning electron microscope (SEM) or a transmission electron microscope (TEM). Among them, from the viewpoint of the quantification accuracy of the area of the domain as the conductive phase, it is preferred to observe using a SEM with a magnification of 1,000 to 100,000. The obtained observed image is binarized and analyzed using an image analysis device or the like to obtain the above ratio. The specific steps will be described later.
[0124] In addition, in order to further reduce the electric field concentration between domains, it is preferred to make the outer shape of the domain closer to a sphere. For this reason, it is preferred to control the domain diameter to be small. Examples of the method include: in the step of preparing a rubber composition in which a domain of CMB is formed in the matrix of MRC by kneading MRC and CMB so that phase separation occurs between MRC and CMB, a method of controlling the domain diameter of CMB to be small. When the domain diameter of CMB decreases, the total specific surface area of CMB increases, and the interface with the matrix increases, so the tension for reducing tension acts on the interface of the domain of CMB. As a result, the outer shape of the domain of CMB is closer to a sphere. Therefore, the value of A / B can be easily controlled to 1.00 to 1.10.
[0125] Here, Taylor's formula (formula (1)), Wu's empirical formula (formula represented by formulas (2) and (3)), and Tokita's formula (formula (4)) are known as factors for determining the domain diameter D in a matrix-domain structure formed when two incompatible polymers are melt-kneaded. (Sumitomo Chemical Co., Ltd., 2003-II, 42)
[0126] Taylor formula
[0127] D = [C·σ / ηm·γ]·f(ηm / ηd) (1)
[0128] Wu's empirical formula
[0129] γ·D·ηm / σ = 4(ηd / ηm) 0.84 ·ηd / ηm > 1 (2)
[0130] γ·D·ηm / σ = 4(ηd / ηm) -0.84 ·ηd / ηm < 1 (3)
[0131] ·Tokita formula
[0132]
[0133] In formula (1) to formula (4), D represents the domain diameter of CMB (maximum Feret diameter Df), C represents a constant, σ represents the interfacial tension, ηm represents the viscosity of the matrix, and ηd represents the viscosity of the domain. In formula (4), γ represents the shear rate, η represents the viscosity of the mixed system, P represents the collision coalescence probability, represents the domain phase volume, and EDK represents the domain phase fracture energy.
[0134] According to the above formulas (1) to (4), in order to reduce the domain diameter D of CMB, for example, it is effective to control the physical properties and kneading conditions of CMB and MRC in step (iii). Specifically, it is effective to control the following four items (a) to (d).
[0135] (a) The difference in interfacial tension σ between CMB and MRC
[0136] (b) Ratio of the viscosity of CMB (ηd) to the viscosity of MRC (ηm) (ηm / ηd)
[0137] (c) In step (iii), the shear rate (γ) and the shear energy (EDK) when kneading CMB and MRC
[0138] (d) Volume fraction of CMB relative to the kneaded product of CMB and MRC in step (iii)
[0139] (a) Difference in interfacial tension between CMB and MRC
[0140] Generally, when two types of incompatible rubbers are mixed, phase separation occurs. This is because, since the interaction between the same polymers is stronger than the interaction between heterogeneous polymers, the same polymers aggregate with each other, and the free energy is reduced and stabilized. Since the interface of the phase separation structure is in contact with heterogeneous polymers, the free energy is higher than the interior stabilized by the interaction between the same molecules. As a result, in order to reduce the free energy of the interface, interfacial tension is generated to reduce the area in contact with the heterogeneous polymer. In the case where the interfacial tension is small, in order to increase entropy, even heterogeneous polymers tend to be mixed more uniformly. The state of uniform mixing is dissolution, and the SP value, which is a measure of solubility, tends to be associated with the interfacial tension. That is, it is believed that the difference in interfacial tension between CMB and MRC is related to the difference in SP values between CMB and MRC. Therefore, it can be controlled by the combination of MRC and CMB, especially the combination of the first rubber and the second rubber.
[0141] The absolute value of the difference in solubility parameter (SP value) between the first rubber in MRC and the second rubber in CMB is 0.4 to 5.7 (J / cm 3 )0.5 The combination of is preferred, especially when the absolute value of the difference in SP value is 0.4 to 4.7 (J / cm 3 ) 0.5 The combination of is preferred, and the absolute value of the difference in SP value is 0.4 to 3.0 (J / cm 3 ) 0.5 By using a combination of rubbers having an absolute value of the difference in SP value within the above range, a phase separation structure can be formed more stably, and the domain diameter D of CMB can be reduced.
[0142] SP value of the first rubber (J / cm 3 ) 0.5 It is preferably 16.8 to 22.0, more preferably 17.0 to 21.7.
[0143] SP value of the second rubber (J / cm 3 ) 0.5 It is preferably 15.8 to 22.0, more preferably 16.0 to 20.0.
[0144] Preferred combinations of the first rubber and the second rubber include, for example, the following combinations on the premise that the absolute value of the difference in SP value is within the above range.
[0145] The first rubber is NBR and the second rubber is SBR,
[0146] The first rubber is SBR and the second rubber is NBR,
[0147] The first rubber is NBR and the second rubber is EPDM,
[0148] The first rubber is SBR and the second rubber is EPDM,
[0149] The first rubber is NBR and the second rubber is IR, or
[0150] The first rubber is BR and the second rubber is NBR.
[0151] SP value measurement method
[0152] By making a calibration curve using a material with a known SP value, the SP values of the first rubber and the second rubber contained in each of MRC and CMB can be accurately calculated. As a known SP value, the catalog value of the material manufacturer can also be used. For example, the SP value of NBR and SBR is almost determined by the content ratio of acrylonitrile or styrene, and does not depend on the molecular weight. Therefore, analytical methods such as pyrolysis gas chromatography (Py-GC) and solid NMR are used to analyze the content ratio of acrylonitrile or styrene in the rubber constituting the matrix and the domain. Then, the SP value can be calculated based on the content ratio of the calibration curve obtained from the material with a known SP value. The SP value of isoprene rubber is determined by the isomeric structures of 1,2-polyisoprene, 1,3-polyisoprene, 3,4-polyisoprene, cis-1,4-polyisoprene, and trans-1,4-polyisoprene. Therefore, similarly to SBR and NBR, the isomer content ratio is analyzed by Py-GC or solid NMR, and the SP value can be calculated from the material with a known SP value.
[0153] The SP value of a material with a known SP value is obtained by the Hansen sphere method.
[0154] (b) Viscosity ratio between CMB and MRC
[0155] As the viscosity ratio (ηd / ηm) between CMB and MRC approaches 1, the maximum Feret diameter of the domain can be made smaller. The viscosity ratio between CMB and MRC can be adjusted by selecting the Mooney viscosity of CMB and MRC and the type and amount of the blended filler. Plasticizers such as paraffin oil can also be added to an extent that does not hinder the formation of a phase separation structure. The viscosity ratio can be adjusted by adjusting the temperature during kneading. The viscosity of CMB or MRC can be measured by measuring the Mooney viscosity ML at the rubber temperature during kneading according to JIS K6300-1:2013 (1+4) Come out.
[0156] (c) Shear rate and shear energy when kneading MRC and CMB
[0157] As the shear rate when kneading MRC and CMB increases and the energy during shearing increases, the maximum Feret diameter Df of the domain can be made smaller.
[0158] The shear rate can be increased by increasing the inner diameter of a stirring member such as a blade or screw of a kneader, reducing the gap from the end surface of the stirring member to the inner wall of the kneader, or increasing the rotation speed. The energy during shearing can be increased by increasing the rotation speed of the stirring member or increasing the viscosity of the first rubber in the CMB and the second rubber in the MRC.
[0159] (d) Volume fraction of domains (volume fraction of CMB relative to the kneaded product of CMB and MRC)
[0160] The volume fraction of CMB relative to the kneaded product of CMB and MRC is related to the probability of collision and coalescence of CMB and MRC. Specifically, when the volume fraction of CMB relative to the kneaded product of CMB and MRC is reduced, the probability of collision and coalescence of CMB and MRC is reduced. That is, by reducing the volume fraction of the domain in the elastic layer within the range that can obtain the desired conductivity, the size of the domain can be reduced.
[0161] Methods for Confirming Matrix-Domain (MD) Structure
[0162] The matrix-domain structure can be confirmed, for example, by the following method: That is, a thin slice of the elastic layer is cut out from the elastic layer to prepare a sample for observation. Examples of means for cutting out a thin slice include a razor blade, a microtome, and FIB.
[0163] If necessary, the observation sample is subjected to a treatment that can help distinguish the matrix and the domain (such as a dyeing treatment and a deposition treatment). Then, the observation sample is observed with a laser microscope, SEM or TEM. A more specific process will be described later.
[0164] Methods for measuring the perimeter of a domain, the perimeter of its envelope, the number of domains, and the average number of domains
[0165] The method for measuring the perimeter of a domain, the envelope perimeter, and the number of domains may be performed, for example, as follows.
[0166] First, prepare section by the same method as the method in the measurement of the volume resistivity of above-mentioned matrix. Subsequently, thin slice with fracture surface can be formed by lower freeze fracture method, cross polisher method or focused ion beam (FIB) method etc. Considering the smoothness of fracture surface and the pretreatment of observation, FIB method is preferred. In addition, in order to suitably observe matrix-domain structure, pretreatment such as dyeing process or deposition process can be carried out, to suitably obtain the contrast between conductivity phase and insulation phase.
[0167] The slice after fracture surface formation and pretreatment can be observed by SEM or TEM. Among them, observation by SEM at a magnification of 1,000 to 100,000 is preferred from the viewpoint of quantification accuracy of the domain perimeter and envelope perimeter.
[0168] The measurement of the perimeter of the domain, the envelope perimeter and the number of domains can be obtained by quantizing the captured image as described above. Using image processing software such as the trade name: Image-Pro Plus (manufactured by Planetron, Inc.), the fracture surface image obtained by observation with SEM is grayed 8-bit to obtain a monochrome image of 256 gray levels. Next, the black and white of the image is reversed in such a way that the domains within the fracture surface become white, and binarization is performed. Then, the perimeter, envelope perimeter and number of domains can be calculated from each domain group in the image. A more specific process will be described later.
[0169] For the above measurement, when the length of the electrophotographic member in the longitudinal direction is L, a sample section is cut from a total of three points, namely, the center in the longitudinal direction and L / 4 from both ends toward the center (i.e., L1 / 4, L2 / 4, and L3 / 4). A plane parallel to the longitudinal direction of the electrophotographic member is cut from the surface layer side of the cut section, and the above observation is performed using a plane having a depth region (region B) of 5 to 6 μm in the elastic layer direction from the elastic layer / surface layer interface.
[0170] In order to satisfy requirement (B), in the step of forming the rubber composition for elastic layer formation on the substrate in step (iv), it is preferred that the domains near the outer surface of the elastic layer are aggregated when forming the elastic layer.
[0171] Figure 2 Schematic diagram of a crosshead extruder 40. The crosshead extruder 40 is a device for uniformly coating the elastic layer-forming rubber composition prepared in step (iii) on the entire circumference of the conductive substrate to produce an unvulcanized rubber roller including the conductive substrate at the center.
[0172] The crosshead extruder 40 includes a crosshead 44 for supplying a conductive substrate 41 and a rubber composition 42 for forming an elastic layer, and a conveying roller 45 for supplying the conductive substrate 41 to the crosshead 44. In addition, a cylinder 46 for supplying the rubber composition 42 for forming an elastic layer to the crosshead 44 is provided.
[0173] The conveying roller 45 continuously supplies the plurality of conductive substrates 41 in the axial direction to the crosshead 44. The cylinder 46 includes a screw 47 therein, and supplies the elastic layer-forming rubber composition 42 to the crosshead 44 as the screw 47 rotates.
[0174] When the conductive substrate 41 is supplied to the crosshead 44, the entire circumference is covered with the elastic layer forming rubber composition 42 supplied to the crosshead from the cylinder 46. Then, the conductive substrate 41 is supplied from the die 48 at the exit of the crosshead 44 as an unvulcanized rubber roller 43 with the elastic layer forming rubber composition 42 coated on the surface.
[0175] In crosshead extrusion molding, the conductive substrate 41 is coated with the elastic layer forming rubber composition 42 by using a tubular die at the front end of the crosshead. Since the outer surface side of the elastic layer forming rubber composition 42 is subjected to friction with the inner wall portion of the die 48, the shear force applied when the rubber composition is discharged is greater than the shear force applied in the area other than the outer surface. The shear force at the inner wall portion of the die is applied in the non-depth direction of the unvulcanized rubber roller, that is, in the direction parallel to the extrusion direction, whereby the domain existing on the outermost surface of the unvulcanized rubber roller is stretched in the non-depth direction.
[0176] In addition, when the rubber composition compressed by the extruder is extruded from the front end of the die head, the pressure is released, and the rubber composition after extrusion expands in the thickness direction (die swelling effect). This expansion is affected by shear rate, and the larger the shear rate, the larger the expansion when the pressure is released. The shear rate increases with the increase of the rubber flow rate. In the die head wall portion, because the friction between the wall and the flowing rubber causes the flow rate of rubber to decrease, the expansion of the rubber after extrusion is small. On the other hand, because the rubber flowing in the region of the inner side of the outer surface without friction with the wall has a high flow rate of rubber, the rubber after extrusion expands greatly. Therefore, after extrusion, the domain is transferred from the internal region with large expansion to the outer surface side with small expansion.
[0177] The domains extend in the non-depth direction in the die inner wall portion and are transferred to the outer surface of the domains when extruded from the die, whereby the domains gather near the outer surface of the elastic layer-forming rubber composition. Thus, an elastic layer satisfying requirement (B) can be formed.
[0178] By reducing the inner diameter of the die or increasing the flow rate of the rubber during extrusion, the phenomenon of domain stretching and the phenomenon of domain migration to the outer surface become more obvious, which is more preferable as a production condition.
[0179] In addition, as the domain size decreases, the transfer of the domain to the outer surface is significant. In order to reduce the size of the domain, there is a method of reducing the difference in SP value between the first rubber in the matrix and the second rubber in the domain. Therefore, as described above, it is more preferable to use a rubber with a small difference in SP value between the two.
[0180] In ρ A represents the volume resistivity of region A, ρ B When the volume resistivity of region B is represented, it is preferable to satisfy ρ B / ρ A ≥10.0. B / ρ A More preferably, it is 30.0 to 90.0. B / ρ A When the content is within the above range, stagnation of charge transfer at the elastic layer / surface layer interface can be suppressed.
[0181] ρ B / ρ A The above range can be controlled by the same method as the method of transferring the domains to the outer surface of the elastic layer to satisfy requirement (B).
[0182] Surface layer
[0183] The surface layer contains an electronic conductive agent. When the surface layer is formed in a form in which the electronic conductive agent is dispersed and contained in a binder resin, the dispersion is fully carried out, which is also preferred in terms of the physical durability of the surface layer. That is, the surface layer preferably contains a binder resin and an electronic conductive agent dispersed in the binder resin. As required, the surface layer may contain roughening particles, a surface release agent, etc.
[0184] Electronic conductive agent
[0185] Examples of the electronic conductive agent contained in the surface layer include conductive particles, such as conductive carbon black, titanium oxide, tin oxide, and metal oxide conductive particles of zinc oxide, and metal conductive particles of aluminum, iron, copper, and silver. That is, the electronic conductive agent is preferably conductive particles. These conductive particles can be used alone or in combination of two or more thereof.
[0186] As conductive particles, composite particles obtained by coating silica particles with conductive particles can also be used. The conductive particles used for the surface layer preferably include carbon black. Since carbon black has a low specific gravity and high conductivity, sufficient conductivity as the surface layer can be ensured by adding a small amount of carbon black to the binder resin. In the present disclosure, since it is preferred to keep the hardness of the surface layer low, it is suitable for carbon black to be added in a small amount.
[0187] The content of the electron conductive agent is preferably 10 to 40 parts by mass, more preferably 15 to 30 parts by mass, based on 100 parts by mass of the binder resin.
[0188] Binder resin
[0189] As the binder resin, known binder resins can be used. Examples thereof include various synthetic resins, natural rubber, vulcanized natural rubber, and rubbers such as synthetic rubber. As the binder resin, fluororesins, polyamide resins, acrylic resins, polyurethane resins, silicone resins, butyral resins, styrene-ethylene-butene-olefin copolymers, and olefin-ethylene-butene-olefin copolymers can be used.
[0190] The binder resin may be used alone, or two or more thereof may be used in combination.
[0191] The binder resin preferably includes a polyurethane resin. The polyurethane resin is preferably at least one selected from the group consisting of a polyester polyurethane obtained by copolymerizing a polyester polyol with a polyisocyanate, a polycarbonate polyurethane obtained by copolymerizing a polycarbonate polyol with a polyisocyanate, and a polyurethane obtained by copolymerizing an ε-caprolactone-modified polyol with a polyisocyanate.
[0192] Among them, in order to achieve both the softness by reducing the universal hardness of the surface layer and the high resistivity of the surface layer, the binder resin is particularly preferably a resin including a polycarbonate structure. Since the polycarbonate structure has low polarity, the volume resistivity of the binder resin itself can be maintained high. Specifically, a polycarbonate-based polyurethane obtained by copolymerizing a polycarbonate polyol with a polyisocyanate is preferred.
[0193] Examples of the polycarbonate polyols include the following: polynonamethylene carbonate diol, poly(2-methyl-octamethylene) carbonate diol, polyhexamethylene carbonate diol, polypentamethylene carbonate diol, poly(3-methylpentamethylene) carbonate diol, polytetramethylene carbonate diol, polytrimethylene carbonate diol, poly(1,4-cyclohexanedimethylene carbonate) diol, poly(2-ethyl-2butyl-trimethylene) carbonate diol, and random / block copolymers thereof.
[0194] The polyisocyanate is selected from commonly used known polyisocyanates, examples of which include the following: toluene diisocyanate (TDI), diphenylmethane diisocyanate (MDI), polymeric diphenylmethane polyisocyanate, hydrogenated MDI, xylene diisocyanate (XDI), hexamethylene diisocyanate (HDI), and isophorone diisocyanate (IPDI), etc. Among them, aromatic isocyanates such as toluene diisocyanate (TDI), diphenylmethane diisocyanate (MDI), and polymeric diphenylmethane polyisocyanate are more preferably used.
[0195] General hardness of surface layer
[0196] In order to suppress the generation of pollutants themselves, it is effective that the toner does not break or deform. For this reason, the surface layer is preferably flexible. As a measure of the hardness of the electrophotographic member, the universal hardness at a position 1 μm deep from the outer surface of the surface layer "universal hardness (t = 1 μm position)" is preferably 1.0 to 7.0 N / mm 2 , more preferably 2.0 to 5.0 N / mm 2 .
[0197] Since the size of the external additive or toner is in the order of submicron to several microns, it is preferable to control the hardness of the very near outer surface which is the contact surface between the surface layer and the external additive or toner. Specifically, by setting the universal hardness of the surface to 1.0 N / mm when the indenter is pressed 1 μm from the outer surface of the surface layer, 2 In the above, it is easy to suppress the occurrence of image density unevenness due to deformation of the charging roller, which is generated when the charging roller and the electrophotographic photosensitive member are in contact with each other in a stationary state for a long time. In addition, by setting the universal hardness to 7.0 N / mm 2Hereinafter, deformation and cracking of the toner can be suppressed, and thus the absolute amount of the deformed toner and the pulverized toner remaining on the photosensitive member can be suppressed more reliably.
[0198] In addition, by setting the universal hardness to 5.0 N / mm 2 Next, the surface layer deforms following the contaminant, and therefore, the number of contact points between the contaminant and the protrusion increases due to the electron conductive agent exposed on the surface of the surface layer, and the injection efficiency of electrons from the protrusion to the contaminant is improved. The universal hardness (t = 1 μm position) can be controlled by the molecular weight of the polyol component, the ratio between the polyol component and the polyisocyanate component, etc.
[0199] The universal hardness of the surface as the surface layer of the charging roller is measured, for example, using a universal hardness tester (product name: FISCHERSCOPE HM2000XYp, manufactured by Fischer Instrumentation).
[0200] Universal hardness is a physical property value obtained by pressing the indenter into the object being measured while applying a load, and is expressed as "(test load) / (surface area of the indenter under the test load) (N / mm 2 )". While applying a predetermined relatively small test load, an indenter such as a quadrangular pyramid is pressed into the object to be measured, and when a predetermined indentation depth is reached, the surface area in contact with the indenter is obtained from the indentation depth, and the universal hardness is obtained from the above formula. A more specific process will be described later.
[0201] Surface layer protrusions originating from the electron conductive agent
[0202] In order to inject charge into the pollutant, it is preferred that there are convex portions originating from the exposed portion of the electronic conductive agent (conductive particles) on the surface of the surface layer. The size of the convex portion originating from the exposed portion of the electronic conductive agent is preferably 5.0 to 100.0 nm. By setting the size to 5.0 nm or more, the convex portion can serve as a starting point for more effectively injecting charge into the pollutant. In addition, by setting the size to 100.0 nm or less, excessive injection of charge into the photosensitive member can be suppressed. The size of the convex portion refers to the average value (number average particle size) of the particle size of the electronic conductive agent in the portion exposed from the binder resin. As a method for measuring the size of the convex portion, an image of a 2 μm square area is taken using a SEM, and the particle sizes of 20 particles randomly selected from the obtained image are measured to obtain the arithmetic mean particle size.
[0203] In addition, it is preferred that the outer surface of the surface layer has a convex portion derived from the exposed portion of the electron conductive agent. In order to inject charge into the pollutant using the convex portion derived from the electron conductive agent, it is effective to control the number of convex portions. In the region of 2.0 μm in length and 2.0 μm in width (4.0 μm2 In the region of the photosensitive member, the number of convex portions originating from the exposed portion of the electronic conductive agent is preferably 50 to 500, and more preferably 200 to 400. By setting the number to 50 or more, the number of convex portions serving as the starting point for injecting charge into the pollutant can be ensured. In addition, when the number is 500 or less, the injection of charge into the photosensitive member can be suppressed. The number of convex portions can be calculated by taking an image of a 2 μm square area using a scanning electron microscope (SEM) and calculating the number of conductive points from the binarized image.
[0204] Next, a method for exposing the electron conductive agent (conductive particles) on the surface of the surface layer will be described. When the surface layer is formed on the elastic layer of the electrophotographic member by a dip coating method, the surface layer is always formed on the outermost surface of the surface layer. Therefore, it is effective to remove the outermost surface layer to expose the electron conductive agent on the outer surface of the surface layer and generate a convex portion on the outer surface of the surface layer through the exposed portion.
[0205] For example, by ultraviolet treatment, grinding, electrolytic grinding, chemical grinding, or ion grinding, etc., the surface layer made of binder resin is removed, and the electronic conductive agent is exposed on the outer surface of the surface layer, so it is easy to form a convex portion. In the present disclosure, since the hardness of the surface layer is low, even by ultraviolet treatment, the surface layer can be fully removed, and the electronic conductive agent can be exposed on the surface of the surface layer. Ultraviolet treatment is preferred because compared with grinding, etc., it is possible to expose the electronic conductive agent on the surface of the surface layer while minimizing the damage to the surface layer.
[0206] The exposed state of the electronic conductive agent can be confirmed using an atomic force microscope (AFM). A height image is obtained in the tapping mode of the AFM. In this case, the portion of the exposed portion originating from the electronic conductive agent is confirmed as a convex portion. When the height image is obtained in the state where the surface layer after dip coating is present, the convex portion cannot be confirmed. In addition, a phase image is obtained in the tapping mode of the AFM. In this case, since the phase shift of the electronic conductive agent is small and the hardness difference between the binder resin and the electronic conductive agent is large, an image with a very large grayscale contrast difference is obtained. When the phase image is obtained in the state where the surface layer after dip coating is present, an image with a very small phase difference and a low contrast difference is obtained.
[0207] Roughening particles
[0208] The surface layer may contain roughening particles as long as the effects of the present disclosure are not impaired. Examples of roughening particles include the following: organic insulating particles such as acrylic resins, polycarbonate resins, styrene resins, polyurethane resins, fluororesins, and silicone resins; and inorganic insulating particles such as particles of titanium oxide, silicon dioxide, aluminum oxide, magnesium oxide, strontium titanate, barium titanate, barium sulfate, calcium carbonate, mica, zeolite, and bentonite.
[0209] In the present disclosure, it is preferred to use flexible organic insulating particles as roughening particles to increase the chance of contact with pollutants such as external additives and toners due to deformation of the surface layer. These particles may be used alone, or a combination of two or more thereof may be used. The number average particle size of the roughening particles is not particularly limited, but is, for example, 3 μm or more and 30 μm or less.
[0210] Ion conductive agent
[0211] The surface layer may contain an ionic conductive agent as long as the effect of the present disclosure is not impaired. In order to transport and supply the charge from the elastic layer to the attached dirt, it is necessary to contain an electronic conductive agent with good responsiveness in the surface layer, but an ionic conductive agent with relatively low (slow) responsiveness may be added as a supplement. As a result, at a certain moment, the charge that can be provided to the dirt on the surface is added to the charge instantly transported from the elastic layer by the electronic conductive agent and the charge that leaves the elastic layer earlier and is transported by the ionic conductive agent with delay. Therefore, when the electronic conductive agent mainly transports the charge, the possibility of insufficient charge supply is further reduced.
[0212] The ion conductive agent is not particularly limited as long as it is an ion conductive agent that exhibits ion conductivity, and examples thereof include the following: inorganic ionic substances such as lithium perchlorate, sodium perchlorate, and calcium perchlorate; quaternary ammonium salts such as lauryltrimethylammonium chloride, stearyltrimethylammonium chloride, and tetrabutylammonium perchlorate; organic acid inorganic salts such as lithium trifluoromethanesulfonate and potassium perfluorobutanesulfonate. These may be used alone, or two or more thereof may be used in combination.
[0213] Among ion conductive agents, when the ion conductive agent has a functional group that easily forms a bond with a material constituting the surface layer, the ion conductive agent is fixed inside the surface layer, so it is easy to maintain the characteristics for a long time, so it is preferred. As an example, when there is a carbamate bond in the surface layer, it is an ion conductive agent with an OH group. More preferably, the ion conductive agent preferably has an imidazolium structure in its structure. Since it is easy to delocalize the charge on the imidazolium ring and it is difficult to produce an uneven distribution of charge in the structure, uniform charge transfer in the surface layer and more uniform charge supply to the dirt can be expected.
[0214] Since the ion conductive agent serves as an auxiliary to the electron conductive agent, the amount of the ion conductive agent is smaller than that of the electron conductive agent constituting the surface layer, and is preferably 0.01 to 5.0 parts by mass with respect to 100 parts by mass of the binder resin. The content is more preferably 0.01 to 2.0 parts by mass.
[0215] Other additives
[0216] Without impairing the effects of the present disclosure, other additives may be added to the surface layer as needed. As additives, chain extenders, crosslinking agents, pigments, silicone additives, amines as catalysts, or tin complexes, etc. may be added. When silicone additives are added to the surface layer, in order to increase the resistance of the surface layer, apply slip to the surface layer, suppress the injection of charges into the photosensitive member, and improve the wear resistance of the surface layer, it is particularly preferred to add silicone additives.
[0217] Layer thickness of the surface layer
[0218] The thickness of the surface layer is preferably 0.1 to 100 μm. The thickness of the surface layer is more preferably 1 to 50 μm, still more preferably 5 to 30 μm, and still further preferably 10 to 30 μm. The layer thickness of the surface layer can be measured by cutting out a roll section with a sharp blade and observing the roll section with an optical microscope or an electron microscope.
[0219] Volume resistivity of the surface layer
[0220] When the electrophotographic member is used as a charging roller, the volume resistivity of the surface layer of the charging roller is preferably 1.0×10 10 ~1.0×10 16 Ω·cm. More preferably, 5.0×10 10 ~1.0×10 16 Ω·cm. When the electrophotographic member is used as a charging roller, it is preferred to set the volume resistivity of the surface layer to a large value. By increasing the volume resistivity of the surface layer, the pollutants are easily returned to the photosensitive member, and the amount of pollutants attached to the charging roller can be further reduced.
[0221] The present inventors believe that when negatively charged pollutants come into direct contact with the surface layer, especially the binder resin on which the electron conductive agent (conductive particles) is not exposed, the negative charge of the pollutants may move to the surface layer side of the charging roller, and the negative charge of the pollutants may decay. In order to suppress the decay of the negative charge of the pollutants, the surface layer preferably has a high resistance, and for this purpose, the volume resistivity of the surface layer is preferably 1.0×10 10 Ω·cm or more.
[0222] In addition, the inventors have confirmed that when the volume resistivity of the surface layer is low, the charge is injected from the charging roller to the photosensitive member. This phenomenon is significant when the hardness of the surface layer is low and when a peripheral speed difference is provided between the charging roller and the photosensitive member. At the time of actual image output, the injected charge amount is added to the charge amount caused by discharge. Therefore, when the injected charge amount is large, it is sometimes difficult to stably maintain the surface potential of the photosensitive member. The reference for the injected charge amount for maintaining the output at a stable image density is 50 V or less, and for this reason, it is more preferable to set the volume resistivity of the surface layer to 1.0×10 10 Ω·cm or more.
[0223] In order to stabilize the discharge as a charging roller, the volume resistivity of the surface layer is preferably 1.0×10 16 Ω·cm or less. The charge amount injected from the charging roller to the photosensitive member can be estimated, for example, as follows.
[0224] In a high temperature and high humidity environment (temperature: 30°C, relative humidity: 80%) with increasing injection charge (e.g. DC-500V), the surface potential of the photosensitive member when a voltage is applied to the charging roller is measured under the condition that the charging roller is not discharged. For the measurement of the volume resistivity of the surface layer, the measured value measured in the conductive mode using an atomic force microscope (AFM) can be adopted. A sheet is cut from the surface layer of the charging roller using a manipulator, and a metal deposition is applied on one surface of the surface layer. A DC power supply is connected to the metal deposition surface, a voltage is applied, the free end of the cantilever is in contact with the other surface of the surface layer, and a current image is obtained through the AFM body. The current value on the surface of 100 randomly selected positions is measured, and the volume resistivity is calculated from the average current value of the top 10 positions of the measured low current value, the average film thickness, and the contact area of the cantilever.
[0225] Method for manufacturing surface layer
[0226] The method for forming the surface layer is not particularly limited, and examples thereof include spraying with a coating obtained by adding a solvent to a raw material, dipping (dip coating method) and roller coating. The dip coating method as a method for forming the surface layer is simple and excellent in production stability. After coating, additional treatments such as heating are performed as required. The method for producing the surface layer preferably includes a step of applying a coating having a raw material of a binder resin and a raw material containing an electronic conductive agent to the outer surface of the elastic layer, and a step of curing the raw material of the binder resin to form the surface layer.
[0227] Processing box
[0228] At least one aspect of the present disclosure provides a process cartridge including the electrophotographic member of the present disclosure. Figure 31 is a schematic cross-sectional view of an electrophotographic process cartridge 100 including an electrophotographic member according to an embodiment of the present disclosure as a charging roller. The process cartridge is configured to integrate a developing device and a charging device and is detachable from a main body of an electrophotographic image forming apparatus.
[0229] The developing device is formed by integrating at least a developing roller 103 , a toner container 106 , and a toner 109 , and may include a toner supplying roller 104 , a developing blade 108 , and a stirring blade 110 as necessary.
[0230] The charging device is formed by integrating at least the photosensitive drum 101 and the charging roller 102, and may include a cleaning blade 105 and a waste toner container 107. A voltage is applied to each of the charging roller 102, the developing roller 103, the toner supplying roller 104, and the developing blade 108.
[0231] Furthermore, the electrophotographic member according to the present disclosure can be used as a charging roller, a developing roller, a developing blade, and a toner supplying roller. The electrophotographic member is preferably a charging member, and the electrophotographic member is more preferably a charging roller.
[0232] Electrophotographic image forming apparatus
[0233] At least one aspect of the present disclosure provides an electrophotographic image forming apparatus including the electrophotographic member of the present disclosure. Figure 4 1 is a schematic configuration diagram of an electrophotographic image forming apparatus 200 using an electrophotographic member according to an embodiment of the present disclosure as a charging roller. The apparatus is a color electrophotographic apparatus to which a process cartridge 100 is detachably mounted. In each process cartridge, toners of respective colors of black BK, magenta M, yellow Y, and cyan C are used.
[0234] The photosensitive drum 201 rotates in the direction of the arrow, is uniformly charged by the charging roller 202 to which a voltage is applied from a charging bias power source, and an electrostatic latent image is formed on its surface by exposure light 211. On the other hand, the toner 209 stored in the toner container 206 is supplied to the toner supply roller 204 by the stirring blade 210, and is conveyed to the developing roller 203. Then, the surface of the developing roller 203 is uniformly coated with the toner 209 by the developing blade 208 arranged in contact with the developing roller 203, and the toner 209 is charged by friction charging. The electrostatic latent image is developed by applying the toner 209 conveyed by the developing roller 203 arranged in contact with the photosensitive drum 201, and is visualized as a toner image.
[0235] The visualized toner image on the photosensitive drum is transferred to the intermediate transfer belt 215 supported and driven by the tension roller 213 and the intermediate transfer belt driving roller 214 by the primary transfer roller 212 to which a voltage is applied by the primary transfer bias power supply. The toner images of the respective colors are sequentially superimposed to form a color image on the intermediate transfer belt.
[0236] The transfer material 219 is fed into the apparatus by a paper feed roller and conveyed between the intermediate transfer belt 215 and the secondary transfer roller 216. A voltage is applied to the secondary transfer roller 216 from a secondary transfer bias power source, and the secondary transfer roller transfers the color image on the intermediate transfer belt 215 to the transfer material 219. The transfer material 219 to which the color image is transferred is subjected to a fixing process by the fixing unit 218, and is discharged outside the apparatus, and the printing operation is terminated.
[0237] On the other hand, the toner remaining on the photosensitive drum and not transferred is scraped off by the cleaning blade 205 and stored in the waste toner storage container 207, and the above process is repeated for the cleaned photosensitive drum 201. In addition, the toner remaining on the primary transfer belt and not transferred is also scraped off by the cleaning device 217.
[0238] Although a color electrophotographic apparatus is shown as an example, in a monochrome electrophotographic apparatus (not shown), a process cartridge is a product that uses only black toner. A monochrome image is formed directly on a transfer material by a process cartridge and a primary transfer roller (without a secondary transfer roller) without using an intermediate transfer belt. Then, the paper is fixed by a fixing unit and discharged to the outside of the apparatus, thereby terminating the printing operation.
[0239] Example
[0240] Hereinafter, the present disclosure will be described based on examples, but the technical scope of the present disclosure is not limited thereto.
[0241] Hereinafter, the charging member in the present disclosure was prepared using the following materials.
[0242] Elastic layer forming material
[0243] NBR
[0244] NBR (1) (trade name: JSR NBR N230SV, acrylonitrile content: 35%, Mooney viscosity ML (1+4) 100℃: 32, SP value: 20.0(J / cm 3 ) 0.5 , manufactured by JSR Corporation, referred to as: N230SV)
[0245] NBR (2) (trade name: Nipol DN401LL, acrylonitrile content: 18.0%, Mooney viscosity ML (1+4)100℃: 32, SP value: 17.4(J / cm 3 ) 0.5 , manufactured by Zeon Corporation, referred to as: DN401LL)
[0246] NBR (3) (trade name: JSR NBR N215SL, acrylonitrile content: 48%, Mooney viscosity ML (1+4) 100℃: 45, SP value: 21.7(J / cm 3 ) 0.5 , manufactured by JSR Corporation, referred to as: N215SL)
[0247] SBR
[0248] SBR (1) (trade name: Tufdene 2000R, styrene content: 25%, Mooney viscosity ML (1+4) 100℃: 45, SP value: 17.0(J / cm 3 ) 0.5 , manufactured by Asahi Kasei Corporation, referred to as: T2000R)
[0249] SBR (2) (trade name: Tufdene 2003, styrene content: 25%, Mooney viscosity ML (1+4) 100℃: 33, SP value: 17.0(J / cm 3 ) 0.5 , manufactured by Asahi Kasei Corporation, referred to as: T2003)
[0250] EPDM
[0251] EPDM (trade name: Esprene 505A, Mooney viscosity ML (1+4) 100℃: 47, SP value: 16.0(J / cm 3 ) 0.5 , manufactured by Sumitomo Chemical Co., Ltd., referred to as: E505A)
[0252] Butadiene rubber BR
[0253] Butadiene rubber (trade name: UBEPOL BR130B, Mooney viscosity ML (1+4) 100℃: 29, SP value: 16.8(J / cm 3 ) 0.5 , manufactured by Ube Corporation, referred to as BR130B)
[0254] Isoprene rubber IR
[0255] Isoprene rubber (trade name: Nipol 2200L, Mooney viscosity ML (1+4) 100℃: 70, SP value: 16.5(J / cm 3 ) 0.5 , manufactured by Zeon Corporation, referred to as: IR2200L)
[0256] Conductive particles
[0257] Carbon black (1) (trade name: TOKABLACK #7270SB, DBP absorption: 62 cm 3 / 100g, manufactured by Tokai Carbon Co., Ltd., referred to as #7270)
[0258] Carbon black (2) (trade name: TOKABLACK #7360SB, DBP absorption: 87 cm 3 / 100g, manufactured by Tokai Carbon Co., Ltd., abbreviated as: #7360)
[0259] Carbon black (3) (trade name: TOKABLACK #5500, DBP absorption: 155 cm 3 / 100g, manufactured by Tokai Carbon Co., Ltd., referred to as: #5500)
[0260] Carbon black (4) (trade name: Raven 1170, DBP absorption: 55 cm 3 / 100g, manufactured by Columbia Chemical, referred to as R1170)
[0261] Carbon black (5) (trade name: MA100, DBP absorption: 95 cm 3 / 100g, manufactured by Mitsubishi Chemical Corporation, referred to as MA100)
[0262] Vulcanizing agent
[0263] Vulcanizing agent (trade name: SULFAX PMC, sulfur content: 97.5%, manufactured by Tsurumi Chemical Industry Co., Ltd., abbreviated as: sulfur)
[0264] Vulcanization accelerator
[0265] Vulcanization accelerator (1) (trade name: Sanceler TBZTD, tetrabenzylthiuram disulfide, manufactured by Sanshin Chemical Industry Co., Ltd., abbreviated as: TBzTD)
[0266] Vulcanization accelerator (2) (trade name: SANTOCURE-TBSI, Nt-butyl-2-benzothiazolesulfenimide, manufactured by FLEXSYS, abbreviated as TBSI)
[0267] Vulcanization accelerator (3) (trade name: NOCCELER EP-60, vulcanization accelerator mixture, manufactured by OUCHI SHINKO CHEMICAL INDUSTRIAL CO., LTD., abbreviated as: EP-60)
[0268] Vulcanization accelerator (4) (trade name: Nocceler TBT, tetrabutylthiuram disulfide, manufactured by OuchiShinko Chemical Industrial Co., Ltd., abbreviated as: TBT)
[0269] filler
[0270] Filler (1) (trade name: Nanox #30, calcium carbonate, manufactured by Maruo Calcium Co., Ltd., abbreviated as #30)
[0271] Packing (2) (Thermax flow form N990, manufactured by CanCab, referred to as MT)
[0272] Surface layer forming material
[0273] A-1: Polyester polyol (trade name: P2010, manufactured by Kuraray Co., Ltd.)
[0274] A-2: Polycarbonate polyol (trade name: T5652, manufactured by Asahi Kasei Chemicals Corporation)
[0275] A-3: ε-caprolactone-modified polyol (trade name: DC2016, manufactured by Daicel Corporation)
[0276] B-3: Isocyanate A / Isocyanate B=4:3 (trade name: VESTANAT B1370, manufactured by Degussa AG / trade name: DURANATE TPA-880E, manufactured by Asahi Kasei Chemicals Corporation)
[0277] C-1: Polyurethane particles (trade name: DAIMIC BEADS UCN-5070D, average particle diameter 7.0 μm, manufactured by Dainichiseika Color & Chemicals Mfg. Co., Ltd.)
[0278] C-2: PMMA particles (trade name: Ganzpearl GM0801, average particle size: 8.0 μm, manufactured by Aica Kogyo Co., Ltd.)
[0279] CB: Conductive carbon black (trade name: MA230, manufactured by Mitsubishi Chemical Corporation, number average particle size: 30 nm)
[0280] D-1: Modified dimethyl silicone oil (trade name: SH-28PA, manufactured by Dow Corning Toray Silicone Co., Ltd.)
[0281] Example 1
[0282] Preparation of charging roller 1
[0283] 1-1. Preparation of domain-forming rubber composition CMB
[0284] The materials of the types and amounts shown in Table 1 were mixed using a pressure kneader to obtain a domain-forming rubber composition CMB.
[0285] The mixing conditions were a filling rate of 70 vol%, a blade rotation speed of 30 rpm, and 18 minutes.
[0286] [Table 1]
[0287]
[0288] 1-2. Preparation of Matrix-Forming Rubber Composition (MRC)
[0289] The materials of the types and amounts shown in Table 2 were mixed using a pressure kneader to obtain a matrix-forming rubber composition (MRC).
[0290] The mixing conditions were a filling rate of 70 vol%, a blade rotation speed of 30 rpm, and 18 minutes.
[0291] [Table 2]
[0292]
[0293] 1-3. Preparation of elastic layer-forming rubber composition 1
[0294] The materials of the types and amounts shown in Table 3 were mixed with an open roll to prepare an elastic layer-forming rubber composition 1. An open roll having a roll diameter of 12 inches was used as a mixer.
[0295] As mixing conditions, the front roll rotation speed was 10 rpm, the rear roll rotation speed was 8 rpm, left and right shearing was performed 20 times in total with a roll gap of 2 mm, and thinning was performed 10 times with a roll gap of 1.0 mm.
[0296] [Table 3]
[0297]
[0298] 1-4. Forming of Conductive Elastic Roller 1
[0299] A round bar having a total length of 252 mm and an outer diameter of 6 mm was prepared by chemically nickel plating the surface of free-cutting steel. Next, an adhesive (trade name: Metaloc U-20, manufactured by Toyo Kagaku Kenkyusho Co., Ltd.) was applied to the entire circumference of the round bar, excluding 11 mm at both ends, over a range of 230 mm, using a roll coater to prepare a substrate.
[0300] Next, the base was coated with the rubber composition 1 for elastic layer formation using a crosshead extruder (manufactured by Mitsuba mfg Co., Ltd.) to prepare a crown-shaped unvulcanized rubber roller. A die with an inner diameter of 9.6 mm was installed at the front end of the crosshead. For each of the barrel, screw and crosshead, the molding temperature was set to 100°C.
[0301] In order to form a crown shape, the substrate was conveyed while changing the conveying speed, and the arithmetic average speed when forming one charging roller was adjusted to 47 mm / sec. At the die exit, the conductive rubber flows out at the same speed as the core metal, so the average flow speed when forming one roller is 47 mm / sec, which is the same as the conveying speed of the substrate.
[0302] The screw speed was adjusted so that the outer diameter of the length center of the unvulcanized rubber roller was 9.8 mm relative to the conveying speed of the substrate. The unvulcanized rubber roller after forming was crown-shaped, with an outer diameter of 9.8 mm at the length center and an outer diameter of 9.7 mm from the length center position to the position of +90 mm at both ends.
[0303] Then, the unvulcanized rubber roller was heated in an electric furnace at 160° C. for 60 minutes for vulcanization, and both ends were cut to set the length of the conductive rubber formed in the axial direction to 232 mm to prepare a conductive elastic roller 1 .
[0304] 2-1. Preparation of surface layer coating liquid 1
[0305] The surface layer coating liquid 1 for forming the surface layer 1 was prepared as follows.
[0306] Under a nitrogen atmosphere, while maintaining the temperature in the reaction container at 65° C., 100 parts by mass of polyester polyol (trade name: P3010, manufactured by Kuraray Co., Ltd.) were gradually added dropwise to 27 parts by mass of polymeric MDI (trade name: Millionate MR200, manufactured by Nippon Polyurethane Industry Co., Ltd.) in the reaction container. After the addition was completed, the mixture was reacted at a temperature of 65° C. for 2 hours. The obtained reaction mixture was cooled to room temperature to obtain an isocyanate group-terminated prepolymer P-1 having an isocyanate group content of 4.3%.
[0307] For 57.0 parts by mass of the isocyanate-terminated prepolymer P-1, 43.0 parts by mass of a polyester polyol (trade name: P2010, manufactured by Kuraray Co., Ltd.) and 23 parts by mass of carbon black (trade name: MA230, manufactured by Mitsubishi Chemical Corporation, number average particle size: 30 nm) were dissolved in methyl ethyl ketone (MEK) to adjust the solid content to 27% by mass. Then, 0.1 parts by mass of a modified dimethyl silicone oil (trade name: SH-28PA, manufactured by Dow Corning Toray Silicone Co., Ltd.) was added to prepare a mixed solution 1.
[0308] In a glass bottle with an internal volume of 450 mL, 270 g of mixed solution 1 and 200 g of glass beads with an average particle size of 0.8 mm were placed and dispersed for 12 hours using a paint oscillating disperser. After dispersion, 15 parts by mass of polyurethane particles with an average particle size of 7.0 μm (trade name: DAIMIC BEADS UCN-5070D, manufactured by Dainichiseika Color & Chemicals Mfg. Co., Ltd.) were added. Then, the dispersion was further dispersed for 15 minutes, and the glass beads were removed to obtain a surface layer coating solution 1.
[0309] 3-1. Preparation of Charging Roller 1
[0310] The conductive elastic roller 1 was dipped (immersed) in the surface layer coating liquid 1 and then pulled up while the longitudinal direction of the conductive elastic roller 1 was set in the vertical direction and the upper end portion thereof was held. The dipping time for dipping was adjusted to 9 seconds, the pulling-up speed of the roller was adjusted so that the initial speed was 20 mm / sec and the final speed was 2 mm / sec, and the speed was changed linearly with respect to the time between 20 mm / sec and 2 mm / sec.
[0311] After coating, air drying was performed at 23° C. for 30 minutes. Next, drying was performed at 80° C. for 1 hour and at 160° C. for 1 hour in a hot air circulation dryer to form a dry film of the coating film of the surface layer coating liquid 1 on the elastic layer.
[0312] Furthermore, the cumulative light intensity is 9000mJ / cm 2 The surface of the dried film was irradiated with ultraviolet rays of 254 nm in a manner to remove the outermost layer of the dried film to form a surface layer in which the conductive particles (conductive carbon black) in the dried film were exposed on the outer surface. As a light source for ultraviolet rays, a low-pressure mercury lamp (manufactured by Toshiba Lighting & Technology Corporation) was used. In this way, a charging roller 1 according to Example 1 was prepared.
[0313] 4. Characteristic evaluation
[0314] 4-1. Impedance measurement
[0315] The impedance was measured by the following measurement method.
[0316] First, as a pretreatment, platinum was deposited on the outer surface of the charging roller as an electrophotographic member while rotating the charging roller to prepare a measuring electrode (metal film). At this time, a masking tape was used to make an electrode with a width of 1.5 cm and uniform in the circumferential direction. By forming the electrode, the contribution of the contact area between the measuring electrode and the electrophotographic member can be reduced as much as possible by the surface roughness of the electrophotographic member. Next, an aluminum sheet was wound around the electrode without a gap to form a measurement sample.
[0317] Then, an impedance measuring device (trade name: Solartron 1260, 96W, manufactured by Solartron Metrology) was connected from the aluminum sheet to the measuring electrode and the substrate. Impedance was measured at a vibration voltage of 1 Vpp and a frequency of 1.0 Hz in an environment of a temperature of 23° C. and a relative humidity of 50% to obtain an absolute value of impedance.
[0318] The charging roller (length in the longitudinal direction: 230 mm) was divided into five equal regions in the longitudinal direction, and a measuring electrode was formed at one point in each region, a total of five points, and the above measurement was performed. The average value was taken as the impedance of the charging roller.
[0319] The impedance of the charging roller 1 is 4.3×10 5 Ω.
[0320] 4-2. Measurement of film thickness of surface layer
[0321] The film thickness of the surface layer is measured by observing a cross section at a total of 9 locations of the surface layer, i.e., 3 locations in the axial direction and 3 points in the circumferential direction, with an optical microscope or an electron microscope, and the average value is taken as the "film thickness" of the surface layer.
[0322] The film thickness of the surface layer of the charging roller 1 was 10 μm.
[0323] 4-3. Measurement of universal hardness of surface layer
[0324] The universal hardness at a position 1 μm deep from the surface of the surface layer was measured using a universal hardness tester. For the measurement, an ultramicrohardness tester (trade name: FISCHERSCOPE HM-2000, manufactured by Helmut Fischer GmbH) was used. Specific measurement conditions are shown below.
[0325] Measuring indenter: Vickers indenter (surface angle 136, Young's modulus 1140, Poisson's ratio 0.07, indenter material: diamond)
[0326] Measurement environment: temperature 23°C, relative humidity 50%
[0327] Maximum test load: 1.0mN
[0328] Load conditions: The load is applied at a speed proportional to the time at which the maximum test load is reached within 30 seconds. In this evaluation, the load F when the indenter is pushed into the surface of the surface layer at a depth of 1 μm and the contact area A between the indenter and the surface layer at this time are used to calculate the universal hardness by the following calculation formula (1).
[0329] Calculation formula (1): General hardness (N / mm 2 )=F / A
[0330] The general hardness of the charging roller 1 is 3.2N / mm 2 .
[0331] 4-4. Measurement of volume resistivity (Ω·cm) of surface layer
[0332] The volume resistivity of the surface layer was measured in the conductive mode using an atomic force microscope (AFM) (trade name: Q-scope250, manufactured by Quesant). First, the surface layer of the charging roller was cut into sheets with a width of 2 mm and a length of 2 mm using a manipulator, and platinum was deposited on one surface of the surface layer. Next, a DC power supply (trade name: 6614C, Agilent) was connected to the surface of the platinum deposition, 10 V was applied, and the free end of the cantilever was brought into contact with the other surface of the surface layer to obtain a current image through the AFM body. The measurement was performed on the surface of 100 positions randomly selected throughout the surface layer, and the "volume resistivity" was calculated from the average current value of the first 10 positions with low current values and the average value of the film thickness of the surface layer.
[0333] The measurement conditions are as follows.
[0334] ·Measurement method: contact
[0335] Cantilever: CSC17
[0336] Measuring range: 10μm×10μm
[0337] Scan rate: 4Hz
[0338] Applied voltage: 10V
[0339] The volume resistivity of the surface layer of the charging roller 1 is 6.8×10 10 Ωcm.
[0340] 4-5. Measurement of convex portion originating from exposed portion of electron conductive agent on outer surface of surface layer
[0341] The method for measuring the number of protrusions originating from the exposed portion of the electronic conductive agent on the surface of the surface layer is as follows. First, the elastic layer including the surface layer is cut out from the charging roller. Next, a scanning probe microscope (SPM) (product name: MFP-3D-Origin, manufactured by Aqualam Technologies, Inc.) is used to perform tapping measurements with a cantilever in an area of 2.0 μm long × 2.0 μm wide to obtain a height image. The obtained height image is binarized using image processing software (product name: Igor-Pro, manufactured by Hulinks, Inc.) to extract protrusions of 5 nm or more in the height image and calculate the number of protrusions. SPM height images are acquired at five locations, and the arithmetic mean of the calculated number of protruding particles is taken as the number of fine protrusions according to the present disclosure.
[0342] The measurement conditions are shown below.
[0343] Measurement mode: AM-FM mode tapping measurement
[0344] Cantilever: SI-DF3
[0345] Measuring range: 2μm×2μm
[0346] The number of micro-convex portions generated by the exposure of the electron conductive agent of the charging roller 1 was 210.
[0347] 4-6. Calculation of the domain ratio between region A and region B in the elastic layer
[0348] The observation slice for calculating the domain ratio between the region A and the region B in the elastic layer was prepared by the following method.
[0349] Slices parallel to the length direction of the charging roller and parallel to the outer surface were cut out at intervals of 1 μm in thickness. The slices were taken out at a cutting temperature of -100°C using a microtome (trade name: Leica EM FCS, manufactured by Leica Microsystems).
[0350] Among the slices prepared at intervals of 1 μm in the thickness direction by the above method, a first slice (slice A) obtained by switching from the surface layer to the elastic layer and a slice (slice B) obtained by further cutting 5 μm toward the elastic layer from slice A were used. The surface of the elastic layer side of slice A was included in region A. Slice B was included in region B. Platinum deposition was performed on the first surface included in region A of slice A and on the second surface included in region B of slice B.
[0351] Next, a scanning electron microscope (SEM) (trade name: S-4800, manufactured by Hitachi High-Technologies Corporation) was used to capture the cross-sectional image at a magnification of 1000 times. The obtained image was gray-scaled by 8 bits using image analysis software (product name: ImageProPlus, manufactured by Media Cybernetics Inc.) to obtain a monochrome image with 256 gray levels. Next, the monochrome of the image was inverted in such a way that the second phase in the monochrome image became white, and a binarization threshold was set for the brightness distribution of the image based on Otsu's discriminant analysis algorithm to obtain a binary image.
[0352] A square with a side length of 100 μm was cut out from the obtained binary image, and the total area of the second phase of the observation area (the first observation area in slice A and the second observation area in slice B) was calculated. The total area of the second phase is the total area of the white area of the binary image. The area of the second phase calculated from slice A is defined as AR12, and the area of the second phase calculated from slice B is defined as AR22. AR11 and AR21 are the areas of the cut observation area, and the areas are calculated from the square with a side length of 100 μm.
[0353] When the length of the elastic layer in the longitudinal direction is L, observation slices are prepared at three points, namely, L1 / 4, L2 / 4, and L3 / 4, and the average value of the values at the three points in total is taken as the value of AR12 and AR22.
[0354] The domain ratio AR12 / AR11 in the region A of the charging roller 1 was 0.52, and the domain ratio AR22 / AR21 in the region B was 0.24.
[0355] 4-7. Determination of the matrix-domain structure (MD structure) in the elastic layer region B
[0356] The determination was performed using the binarized image of slice B acquired in 4-6 above. Using the same image processing software as in 4-6 above and using the counting function of the software, the percentage K of the number of domains that were not connected to each other but isolated was calculated relative to the total number of domains that existed in a 50 μm square area and did not contact the frame line of the binarized image.
[0357] When the length of the elastic layer in the longitudinal direction is L, slices for observation are made at three points, L1 / 4, L2 / 4, and L3 / 4, and when the arithmetic mean of K at a total of three points is greater than 80%, the MD structure is judged to be "present", and when the arithmetic mean is less than 80%, the MD structure is judged to be "absent".
[0358] For region B of charging roller 1, the matrix-domain structure "exists" as observed.
[0359] 4-8. Measurement of the circumference and envelope circumference of the domains in region B in the elastic layer, the number of domains and the equivalent circle diameter D
[0360] Platinum deposition was performed on the cutting plane using the slice B prepared in 4-6 above. Next, a cross-sectional image was obtained by shooting at a magnification of 5000 times using a scanning electron microscope (SEM) (trade name: S-4800, manufactured by Hitachi High-Technologies Corporation). The obtained image was grayed 8-bit using image analysis software (product name: ImageProPlus, manufactured by MediaCybernetics Inc.) to obtain a monochrome image of 256 grayscales. Next, the monochrome of the image was inverted in such a way that the domain in the monochrome image became white, and a binarization threshold was set for the brightness distribution of the image based on Otsu's discriminant analysis algorithm to obtain a binary image.
[0361] In the binarized image, a 15 μm square area was cut out, and the cross-sectional area, perimeter, and envelope perimeter were calculated using the counting function of the image processing software.
[0362] For each domain, the domain cross-sectional area S is calculated by d = (S / 2π)0.5 To calculate the equivalent circular diameter d of each domain, and calculate the number average of d as the equivalent circular diameter D of the domain.
[0363] A / B was calculated using the perimeter A and the envelope perimeter B calculated for each domain observed in each observation area, and the ratio (number %) of domains with A / B of 1.00 to 1.10 among all observed domains (required) was obtained. In addition, the arithmetic mean diameter of the domain and the number of domains in the three observation areas were calculated from all observed domains.
[0364] When the length of the elastic layer in the longitudinal direction is L, observation slices are made at three points, L1 / 4, L2 / 4, and L3 / 4, and the average value of the total value of the three points is taken as the ratio of the region where A / B meets the requirements and the average value of A / B.
[0365] The ratio of the charging roller 1 in the region where A / B was 1.00 to 1.10 was 89%, and the arithmetic mean value of A / B was 1.06.
[0366] 4-9. Volume resistivity of region A and region B in the elastic layer and volume resistivity of the matrix in region B
[0367] The volume resistivity of region A was calculated using slice A prepared in 4-6, and the volume resistivity of region B was calculated using slice B.
[0368] Specifically, in an environment with a temperature of 23°C and a relative humidity of 50%, the platinum deposited surface of 4-6 was placed on a metal plate in a state of facing upward, and a voltage of 50V was applied between the metal plate and the platinum deposited surface to measure the current value. The thickness of the slice was set to 1 μm, and the volume resistivity was calculated from the thickness and the current value. In addition, when the length of the elastic layer in the longitudinal direction is L, the elastic layer is prepared at three positions of L1 / 4, L2 / 4, and L3 / 4, and the average value of the total three positions is taken as the volume resistivity of region A and region B, and the volume resistivity ρ of region A is calculated from the volume resistivity ρ of region A. A and ρ B Calculate ρ B / ρ A .
[0369] Next, the volume resistivity of the matrix in the region B was measured by using a scanning probe microscope (SPM) (trade name: Q-Scope 250, manufactured by Quesant Instrument Corporation) operating in a contact mode.
[0370] First, slice B was obtained in the same manner as 4-6. Next, in an environment of 23°C and 50% relative humidity, the slice was mounted on a metal plate, a position directly in contact with the metal plate was selected, and the cantilever of the SPM was brought into contact with the position corresponding to the substrate. Next, a voltage of 50 V was applied to the cantilever, and the current value was measured.
[0371] The surface profile of the measurement slice is observed with SPM, and the thickness at the measurement position is calculated from the obtained height profile. The volume resistivity is calculated from the thickness and the current value to obtain the volume resistivity of the matrix.
[0372] Furthermore, when the length of the elastic layer in the longitudinal direction is L, the elastic layer is prepared at three positions, L1 / 4, L2 / 4 and L3 / 4, and the average value of the three positions is taken as the volume resistivity of the matrix.
[0373] Volume resistivity ratio ρ between region A and region B in the elastic layer of the charging roller 1 B / ρ A The volume resistivity of the matrix is 2.7×10 8 Ωcm.
[0374] 4-10. Ratio S of the cross-sectional area of the conductive particles contained in the domain to the cross-sectional area of the domain C Calculation of / S
[0375] Using the platinum deposition slice B prepared in 4-6 above, a cross-sectional image was obtained by photographing at a magnification of 20,000 times using a scanning electron microscope (SEM) (trade name: S-4800, manufactured by Hitachi High-Technologies Corporation). Next, binarization was performed using image analysis software (product name: ImageProPlus, manufactured by Media Cybernetics Inc.) so that the carbon black in the domain could be distinguished. Further, an observation area having a size accommodating one domain was extracted from the obtained binarized image, and the cross-sectional area S of the domain and the cross-sectional area S of the carbon black as conductive particles contained in the domain were calculated by using a counting function. C , through S C / S is the cross-sectional area ratio of the conductive particles in the calculation domain.
[0376] S of charging roller 1 C / S is 26.7%.
[0377] 5. Evaluation as a charging member
[0378] 5-1. Measurement of injection charge amount of toner
[0379] The ability of the charging roller 1 to supply negative charge to contaminant components such as transfer residual toner and external additives was evaluated as follows.
[0380] A laser printer (trade name: HP LaserJet Pro M203dw, manufactured by HP) was prepared as an electrophotographic image forming device. Then, the motor of the laser printer was modified so that the processing speed was 1.4 times the normal speed. In addition, an external power supply was connected to apply voltage to the charging roller, and the modification was performed to ensure that the voltage was not directly applied to the charging roller from the main unit. In addition, for the process box for the laser printer, the cleaning blade of the charging roller and the developer container in contact with the photosensitive drum were removed. The transfer roller of the laser printer body was also removed.
[0381] The laser printer and the process cartridge were allowed to stand for 48 hours in a low temperature and low humidity environment (temperature: 15°C, relative humidity: 10%). The process cartridge was then loaded into the laser printer. Then, the following evaluation was performed in a low temperature and low humidity environment. In a low temperature and low humidity environment, charge injection from the charging roller to the toner is difficult to occur. By performing the following evaluation in such an environment, the charge injection capability to the charging roller can be more accurately evaluated.
[0382] First, the main body is stopped in the middle of an image forming process of outputting a solid black image under a normal image output condition, and a state is formed in which the entire circumference of the photosensitive drum is covered with a toner layer.
[0383] Next, the process cartridge in a state where the entire circumference of the photosensitive drum is covered with the toner layer is taken out from the main body. The charging roller of the process cartridge is removed, the charging roller 1 is mounted as the charging roller, and the process cartridge is mounted to the main body.
[0384] Then, an image process was performed in which a voltage at which the charging roller does not discharge, specifically -500 V, was applied from an external power source to the charging roller 1 to output a solid white image, and in this process, the potential of the toner on the surface of the toner layer on the photosensitive drum before and after passing through the roller nip portion between the charging roller and the photosensitive drum was measured. For the measurement of the potential, a surface electrometer probe (trade name: MODEL555P-1, manufactured by Trek Japan Co., Ltd.) arranged at a position 2 mm from the surface of the photosensitive drum was used.
[0385] The difference between the surface potential of the toner layer before passing through the nip portion and the surface potential of the toner layer after passing through the nip portion was measured as the injection charge amount (V) of the toner by the charging roller.
[0386] The injection charge amount of the toner by the charging roller 1 was -20.4V.
[0387] 5-2. Measurement of the amount of dirt (toner color density)
[0388] In order to evaluate the amount of dirt adhesion of the charging roller 1, the following evaluation was performed.
[0389] A laser printer (trade name: HP LaserJet Pro M203dw, manufactured by HP) was prepared as an electrophotographic image forming device. Then, the motor of the laser printer was remodeled so that the processing speed was 1.4 times the normal speed. In addition, an external power supply was connected to apply voltage to the charging roller, and the remodeling was performed to ensure that the voltage was not directly applied to the charging roller from the main unit. In addition, for the process box for the laser printer, the cleaning blade of the charging roller was removed. The evaluation environment was the same as 5-1 above.
[0390] First, 500 images were output in which horizontal lines with a width of 2 dots and an interval of 100 dots were drawn in a direction perpendicular to the rotation direction of the photosensitive drum, and the charging roller 1 was removed from the process cartridge to evaluate the degree of contamination by coloration evaluation. The coloration evaluation was performed as follows.
[0391] A polyester adhesive tape (trade name: No.31B, manufactured by Nitto Denko Corporation) is attached to the surface of the charging roller, and then the adhesive tape is peeled off together with the toner attached to the surface of the charging roller, and attached to white paper. This operation is performed on the entire image printing area on the surface of the charging roller, and then the reflection density of the adhesive tape is measured for the entire image printing area with the aid of a photovoltaic reflection densitometer (trade name: TC-6DS / A, manufactured by Tokyo Denshoku Co., Ltd.) to obtain the maximum value. Next, the reflection density of the new polyester adhesive tape also attached to the white paper is measured to obtain the minimum value, and the increase in the reflection density is taken as the value of the coloring density. As the value of the coloring density is smaller, the amount of dirt on the charging roller is smaller and better, so an indicator of the degree of contamination on the charging roller is used.
[0392] The toner coloring concentration of the charging roller 1 was 24%.
[0393] 5-3. Image evaluation
[0394] In the same main body and cartridge configuration as in 5-2 above, 20,000 images in which characters of the letter "E" having a size of 4 points were printed at a print percentage of 1% on A4-sized paper were output under a low temperature and low humidity environment (temperature: 15°C, relative humidity: 10%). Note that the output of the electrophotographic image was performed in a so-called intermittent mode in which the rotation of the electrophotographic photosensitive member was stopped for 7 seconds each time a sheet of paper was output. In the image output in the intermittent mode, the number of frictions between the charging roller and the electrophotographic photosensitive member increased compared to the case of continuously outputting the electrophotographic image, and therefore, it can be said that the image output in the intermittent mode is a more severe evaluation condition for the charging roller.
[0395] Next, a halftone image (an image in which horizontal lines with a width of 1 dot and an interval of 2 dots were drawn in a direction perpendicular to the rotation direction of the photosensitive drum) was output, and the obtained image was visually observed using a magnifying glass and evaluated according to the following criteria.
[0396] Rank A: No white spots were observed even when examined with a magnifying glass.
[0397] Rank B: No white spots were visually observed.
[0398] Rank C: White spots were slightly observed visually.
[0399] Rank D: White spots were visually observed over the entire area.
[0400] No white dots were visually recognized in the halftone image using the charging roller 1 .
[0401] Embodiments 2 to 22
[0402] Charging rollers 2 to 22 were produced in the same manner as in Example 1 except that the elastic layer and the surface layer were formed under the conditions shown in Table 8. Regarding the formulation of the rubber composition for elastic layer formation in each elastic layer numbered in Table 8, CMB was produced with the formulation shown in Table 4, MRC was produced with the formulation shown in Table 5, and the rubber composition for elastic layer formation was produced with the formulation shown in Table 6. In addition, a coating liquid for a surface layer was produced with the formulation shown in Table 7. The number of parts in each table indicates the number of parts by mass.
[0403] Comparative Example 1
[0404] The elastic layer-forming rubber composition 20 was prepared by changing CMB to the blend shown in Table 4, MRC to the blend shown in Table 5, and the conductive rubber composition to the blend shown in Table 6. Then, using the same substrate as that used in Example 1, the substrate was coated with the elastic layer-forming rubber composition 20. The detailed conditions are as follows.
[0405] Using a crosshead extruder (manufactured by Mitsuba Manufacturing Co., Ltd.), a conductive rubber composition 20 is applied to make a crown-shaped unvulcanized rubber roller. A die with an inner diameter of 10.5 mm is mounted to the front end of the crosshead. For each of the barrel, screw and crosshead, the molding temperature is set to 100 ° C. The conveying speed of the substrate is adjusted to 60 mm / second. At the die outlet, the conductive rubber flows out at the same speed as the core metal, so the flow rate of the conductive rubber composition 1 'at the die outlet is 60 mm / second, which is the same as the conveying speed of the substrate. The rotating speed of the screw is adjusted so that the outer diameter of the length center of the unvulcanized rubber roller is 10.3 mm relative to the conveying speed of the substrate.
[0406] Next, the unvulcanized rubber roller was heated in an electric furnace at 160° C. for 60 minutes for vulcanization, and both ends were cut to form a conductive rubber having an axial length of 232 mm.
[0407] Then, the surface of the conductive rubber layer was ground by rotary grinding. Thus, a conductive roller 20 including an elastic layer 20 was obtained, the conductive roller 20 having a diameter of 9.7 mm in the center in the longitudinal direction and a diameter of 9.65 mm at positions 90 mm from the center toward both ends.
[0408] Finally, a surface layer was formed in the same manner as in Example 1, and UV treatment was performed to obtain a charging roller 23. The evaluation results are shown in Tables 8 to 10.
[0409] Comparative Examples 2 and 3
[0410] Charging rollers 24 and 25 were prepared in the same manner as in Comparative Example 1 except that the blend of CMB was changed as shown in Table 4, the blend of MRC was changed as shown in Table 5, and the blend of the elastic layer-forming rubber composition was changed as shown in Table 6. The evaluation results are shown in Tables 8 to 10.
[0411] Table 4 shows the blends of CMBs.
[0412] [Table 4]
[0413]
[0414] Table 5 shows the blends of MRC.
[0415] [Table 5]
[0416]
[0417] [Table 6]
[0418]
[0419] [Table 7]
[0420]
[0421] [Table 8]
[0422]
[0423] [Table 9]
[0424]
[0425] In the table, “Number of domains” is the average value of the number of domains in a 15 μm square observation area placed in region B, and “A / B number %” indicates the number ratio of domains with A / B values of 1.00 to 1.10.
[0426] [Table 10]
[0427]
[0428] While the present invention has been described with reference to exemplary embodiments, it is to be understood that the invention is not limited to the disclosed exemplary embodiments.The scope of the following claims is to be accorded the broadest interpretation so as to encompass all such modifications and equivalent structures and functions.
Claims
1. An electrophotographic member comprising: A substrate having a conductive surface; an elastic layer on said conductive surface of said substrate; and a surface layer in contact with a surface of the elastic layer on the opposite side of the surface facing the substrate, wherein The surface layer comprises an electronically conductive agent, The metal film is provided on the outer surface of the surface layer of the electrophotographic member, and in an environment of a temperature of 23° C. and a relative humidity of 50%, when an alternating voltage with an amplitude of 1 V and a frequency of 1.0 Hz is applied, the impedance between the conductive surface of the substrate and the metal film is within 1.0×10 3 to 1.0×10 8 In the range of Ω, The elastic layer includes an insulating first phase including at least a cross-linked product of a first rubber, and a second phase including conductive particles and a cross-linked product of a second rubber different from the first rubber, The thickness of the elastic layer is at least 10 μm, The elastic layer has a matrix-domain structure in which domains composed of the second phase are dispersed in a matrix composed of the first phase in a region of at least 5 μm in a depth direction of the elastic layer from an interface between the elastic layer and the surface layer, A region having a thickness of 1 μm from the interface between the elastic layer and the surface layer to a position of 1 μm in the depth direction of the elastic layer is defined as region A, and a region having a thickness of 1 μm from the interface to a position of 5 to 6 μm in the depth direction of the elastic layer is defined as region B, When the first surface of the elastic layer in the region A is exposed and a first observation region of a square with a side length of 100 μm is placed on the first surface by a scanning electron microscope, the first observation region includes at least the second phase, A ratio AR12 / AR11 of a total area AR12 of the second phase in the first observation region to an area AR11 of the first observation region is greater than 0.40, and When the second surface of the elastic layer in the region B is exposed and a second observation region of a square with a side length of 100 μm is placed on the second surface by a scanning electron microscope, the matrix-domain structure is observed in the second observation region, and a ratio AR22 / AR21 of a total area AR22 of the second phase in the second observation region to an area AR21 of the second observation region is 0.40 or less.
2. The electrophotographic member according to claim 1, wherein The AR12 / AR11 is greater than 0.
50.
3. The electrophotographic member according to claim 1, wherein When a 15 μm square observation area is placed on the second surface in the area B, the perimeter of the domain is defined as A, and the envelope perimeter of the domain is defined as B, the proportion of the domains having an A / B value of 1.00 to 1.10 is 80% by number or more.
4. The electrophotographic member according to claim 1, wherein The cross-sectional area S of the conductive particles in the region B is C The ratio S relative to the cross-sectional area S of the domain C / S is 20.0% to 30.0%.
5. The electrophotographic member according to claim 1, wherein When A represents the volume resistivity of the region A, and ρ B When the volume resistivity of the region B is expressed as B / ρ A ≥10.
0.
6. The electrophotographic member according to claim 1, wherein The volume resistivity ρm of the matrix in the region B is 1.0×10 8 Ωcm or more and 1.0×10 17 Ωcm or less.
7. The electrophotographic member according to claim 1, wherein The surface layer comprises a binder resin and an electronic conductive agent dispersed in the binder resin, The outer surface of the surface layer has a protrusion derived from the exposed portion of the electron conductive agent, and The universal hardness at a position 1 μm deep from the outer surface of the surface layer is 1.0 to 7.0 N / mm 2 .
8. The electrophotographic member according to claim 1, wherein The first rubber includes at least one selected from the group consisting of isoprene rubber IR, butadiene rubber BR, styrene-butadiene rubber SBR and acrylonitrile-butadiene rubber NBR, and The second rubber includes at least one selected from the group consisting of isoprene rubber IR, butadiene rubber BR, styrene-butadiene rubber SBR, acrylonitrile-butadiene rubber NBR, and ethylene-propylene-diene rubber EPDM.
9. The electrophotographic member according to claim 1, wherein The absolute value of the difference in solubility parameter SP between the first rubber and the second rubber is 0.4 to 5.7 (J / cm 3 ) 0.5 .
10. The electrophotographic member according to claim 9, wherein In a combination of the first rubber and the second rubber, The first rubber is NBR and the second rubber is SBR, The first rubber is SBR and the second rubber is NBR, The first rubber is NBR and the second rubber is EPDM, The first rubber is SBR and the second rubber is EPDM, The first rubber is NBR and the second rubber is IR, or The first rubber is BR and the second rubber is NBR.
11. The electrophotographic member according to claim 1, wherein The electrophotographic member is a charging member.
12. A process cartridge detachable from an electrophotographic image forming apparatus, the process cartridge comprising: The electrophotographic member according to any one of claims 1 to 11.
13. An electrophotographic image forming apparatus comprising: The electrophotographic member according to any one of claims 1 to 11.
14. The electrophotographic image forming apparatus according to claim 13, wherein The electrophotographic image forming apparatus includes an electrophotographic photosensitive member and a charging member that charges the electrophotographic photosensitive member, and the charging member is the electrophotographic member.
Citation Information
Patent Citations
Conductive member, process cartridge, and electrophotographic image forming apparatus
JP2021067946A